Organic tin oxide hydroxide patterning composition, precursor and patterning

By using organic solvents and a coating solution of hydrolyzable metal compounds in situ, forming a radiation-sensitive organic tin oxide hydroxide coating, the inefficiency and complex preparation problems of patterned materials in the prior art are solved, and the problem of achieving the realization of the following methods High resolution and low line width roughness patterning effect.

CN113534609BActive Publication Date: 2024-12-31IMPRIA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202110706883.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2016-02-19
Filing Date
2016-10-12
Publication Date
2024-12-31
Estimated Expiration
2036-10-12

AI Technical Summary

Technical Problem

In the prior art, when forming high-resolution patterned materials, it is difficult to achieve low linewidth roughness and efficient patterning, and the preparation process of resist precursors is complex and unstable, affecting the accuracy of micro and nanofabrication.

Method used

Using a coating solution containing organic solvents and hydrolyzable metal compounds, a radiation-sensitive organic tin oxide hydroxide coating is formed by in situ hydrolysis, and patterned with UV light, EUV light or electron beam radiation, combined with a specific precursor and solvent systems to simplify the preparation process and improve patterning performance.

Benefits of technology

High resolution patterning at low radiation doses is achieved, line width roughness is reduced, the preparation process of resist precursors is simplified, and patterning performance and material stability are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113534609B_ABST
    Figure CN113534609B_ABST
Patent Text Reader

Abstract

The present invention describes an organometallic precursor for forming a high-resolution lithographic patterned coating based on metal oxide hydroxide chemistry. The precursor composition generally comprises a ligand that is susceptible to hydrolysis by water vapor or other OH source composition under appropriate conditions. The organometallic precursor generally comprises an organic ligand that is radiation sensitive to tin, which can produce a coating that is effective for high-resolution patterning at relatively low radiation doses and is particularly suitable for EUV patterning. The precursor composition is easy to process under commercially suitable conditions. The coating can be formed using in-situ hydrolysis or phase processing of a solution based on vapor deposition.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Divisional application

[0002] The present application is a divisional application of application number 201680060193.7, application date October 12, 2016, and titled “Organotin Oxide Hydroxide Patterning Compositions, Precursors and Patterning”.

[0003] CROSS-REFERENCE TO RELATED APPLICATIONS

[0004] This application claims priority to co-pending U.S. Provisional Patent Application No. 62 / 240,812 filed on October 13, 2015 by Meyers et al., entitled “Organotin Oxide Hydroxide Patterning Compositions With Precursor Vapor Deposition,” and also claims priority to co-pending U.S. Provisional Patent Application No. 62 / 297,540 filed on February 19, 2015 by Cardineau et al., entitled “Precursor Compositions for Organotin Oxide Hydroxide Photoresist Films,” both of which are incorporated herein by reference. Technical Field

[0005] The present invention relates to a precursor composition that can be coated and in situ hydrolyzed to form a coating comprising an organotin oxide hydroxide. The present invention further relates to a radiation sensitive organotin oxide hydroxide coating that can be effectively patterned with UV light, EUV light or electron beam radiation to form a high resolution pattern with low line width roughness. Background Art

[0006] For the formation of semiconductor-based devices and other electronic devices or other complex fine structures, materials are often patterned to integrate the structure. Therefore, the structure is usually formed by an iterative process of sequential deposition and etching steps by which the pattern is formed from various materials. In this way, a large number of devices can be formed into a small area. Some developments in the field may involve reducing the footprint of the device, which is desirable for improving performance.

[0007] An organic composition can be used as a radiation-patternable resist such that a radiation pattern is used to alter the chemical structure of the organic composition corresponding to the pattern. For example, the process of patterning a semiconductor wafer may require the transfer of an image desired from thin film lithography of an organic radiation-sensitive material. Patterning of the resist typically involves several steps, including exposing the resist to a selected energy source (such as through a mask) to record a latent image, and then developing and removing selected resist regions. For a positive resist, the exposed regions are converted such that such regions can be selectively removed, while for a negative resist, the unexposed regions are more readily removed.

[0008] Generally, radiation, reactive gases, or liquid solutions can be employed to develop the pattern to remove the selectively sensitive portions of the resist, while the other portions of the resist act as a protective etch-resistant layer. Liquid developers can be particularly effective in developing the latent image. The substrate can be selectively etched through windows or voids in the remaining regions of the protective resist layer. Alternatively, materials can be deposited into the exposed regions of the underlying substrate through the development windows or voids in the remaining regions of the protective resist layer. Finally, the protective resist layer is removed. This process can be repeated to form additional layers of patterned material. The material can be deposited using chemical vapor deposition, physical vapor deposition, or other desired methods. Additional processing steps, such as depositing conductive materials or implanting dopants, can be used. In the fields of micro- and nano-fabrication, the feature sizes of integrated circuits have become extremely small to achieve high integration densities and improve circuit functionality. SUMMARY OF THE INVENTION

[0009] In a first aspect, the present invention relates to a coating solution comprising an organic solvent, a first organometallic composition, and a metal compound having a hydrolyzable ligand-metal bond. In some embodiments, the first organometallic composition can be represented by the formula: formula R z SnO (2-(z / 2)-(x / 2)) (OH) x , where 0 < z ≤ 2 and 0 < (z + x) ≤ 4; formula R n SnX 4-n , where n = 1 or 2, or a mixture thereof, where R is a hydrocarbyl group having 1 to 31 carbon atoms, and X is a ligand having a hydrolyzable M-X bond. The hydrolyzable metal compound can be represented by the formula MX' n , where M is a metal selected from Groups 2 to 16 of the Periodic Table, X' is a ligand having a hydrolyzable M-X' bond or a combination thereof, and n is determined by the metal valence and ligand charge.

[0010] In another aspect, the present invention relates to a coating solution comprising an organic solvent, a first organometallic composition of at least about 10 mole percent relative to the total metal content, and a second organometallic composition of at least 10 mole percent relative to the total metal content. In some embodiments, the first organometallic composition may be represented by the formula: formula R z SnO (2-(z / 2)-(x / 2)) (OH) x , where 0 < z ≤ 2 and 0 < (z + x) ≤ 4; formula R n SnX 4-n , where n = 1 or 2, or a mixture thereof, where R is a hydrocarbon group and Sn-X is a hydrolyzable chemical bond. The second organometallic composition may be represented by the formula R' y SnX' 4-y , where y = 1 or 2, where R' is a hydrocarbon group different from R, and X' is a ligand having a hydrolyzable Sn-X' bond that is the same as or different from X.

[0011] In another aspect, the present invention relates to a method for forming a radiation-patternable coating, the method comprising exposing a precursor coating on a substrate to water vapor, wherein the precursor coating comprises a first organometallic composition and a second hydrolyzable composition. The first organometallic composition may be represented by the formula: formula R z SnO (2-(z / 2)-(x / 2) (OH) x , where 0 < z ≤ 2 and 0 < (z + x) ≤ 4; or R' n SnX 4-n , where n = 1 or 2, and R and R' are independently hydrocarbon groups having 1 to 31 carbon atoms. The second hydrolyzable composition may be: a second organometallic composition represented by the formula R” y SnX' 4-y , where y = 1 or 2 and R” is different from R' and X' is a ligand having a hydrolyzable Sn-X' bond that is the same as or different from X; or an inorganic composition MLv, where v is 2 ≤ v ≤ 6 and L is a ligand having a hydrolyzable M-L bond that is the same as or different from X and X'. In some embodiments, the exposure step causes hydrolysis of the precursor coating compound to form a coating comprising ((R or R') a R” b )SnO (2-((a+b) / 2)-(w / 2)) (OH) w , where 0 < (a + b) ≤ 2 and 0 < (a + b + w) < 4; or comprising y((R or R') a R” b )SnO (2-((a+b) / 2)-(w / 2)) (OH) w ·zMO ((m / 2)-l / 2) (OH) l, where 0<(a+b)≤2, 0<(a+b+w)<4, m=M m+ The present invention relates to a tin-containing metal having a formal valence of 0≤1≤m, y / z=(0.05 to 0.6), and M=M′ or Sn, wherein M′ is a non-tin metal of Group 2 to Group 16 of the periodic table.

[0012] In an additional aspect, the present invention relates to a method for forming a radiation patternable coating comprising a metal oxo-hydroxyl network having metal cations having organic ligands with metal carbon bonds and metal oxygen bonds, the method comprising separately inputting the following into a deposition chamber that is sealed and isolated from the ambient atmosphere: a first precursor vapor comprising a compound R n S X 4-n , wherein n=1 or 2, wherein R is a hydrocarbon group having 1 to 31 carbon atoms, and X is a hydrolyzable or oxidizable ligand; and a second precursor vapor comprising oxygen containing the first precursor vapor capable of hydrolyzing or oxidizing under conditions in the deposition chamber to form a hydrolyzed or oxidized composition. Generally, the substrate can be configured with a surface to receive the hydrolyzed or oxidized composition.

[0013] In other aspects, the present invention relates to a coated substrate comprising a substrate having a surface and a coating on the surface, the surface comprising a z SnO (2-(z / 2)-(w / 2)) (OH) w ·z MO ((m / 2)-l / 2) (OH) l An organometallic composition represented by <z≤2,0<(z+w)≤4,m=M m+ , 0≤l≤m, y / z=(0.05 to 0.6), and M=M′ or Sn, wherein M′ is a non-tin metal of Group 2 to Group 16 of the periodic table, and R is a hydrocarbon group having 1 to 31 carbon atoms.

[0014] Additionally, the present invention relates to substrates and radiation-sensitive coatings comprising a substrate having a radiation sensitivity of no more than about 6.125 mJ / cm 2 A dose-to-gel (Dg) of alkyl metal oxide hydroxide.

[0015] In addition, the present invention relates to a substrate comprising an inorganic semiconductor layer and a radiation-sensitive coating material along a surface thereof. In some embodiments, the coating material can be patterned with EUV light having a wavelength of 13.5 nm in a pattern of 16 nm lines with a spacing of 32 nm to irradiate the coating material with about 8 mJ / cm 2 to about 25mJ / cm 2The radiation sensitive coating material may include a metal such as Sn, and may include at least 5 weight percent of the metal, and in other embodiments at least 20 weight percent of the metal. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 is a schematic perspective view of a radiation patterned structure with a latent image.

[0017] Figure 2 for Figure 1 Side plan view of the structure.

[0018] Figure 3 After developing the latent image to remove the non-irradiated coating material to form a patterned structure Figure 1 A schematic perspective view of the structure of.

[0019] Figure 4 for Figure 3 Side view of the patterned structure.

[0020] Figure 5 After developing the latent image to remove the radiation coating material to form a patterned structure Figure 1 A schematic perspective view of the structure of.

[0021] Figure 6 for Figure 5 Side view of the patterned structure.

[0022] Figure 7 For the formation of a 2 Scanning electron (SEM) micrograph of a regular pattern on a substrate with a line spacing of 16.7 nm formed by EUV dose.

[0023] Figure 8 Graphs of film thickness after exposure and development as a function of EUV dose formed from 50 annular pads of 500 micrometers diameter exposed to a step dose of in situ hydrolysis on a radiation resist coated substrate as described herein.

[0024] Fig. 9 Figure 5 is a graph with two FTIR spectra comparing the films formed by solution-based hydrolysis and in situ hydrolysis in the coating.

[0025] Fig.10 A set of EUV contrast graphs as a function of dose for coatings formed from three different amounts of Sn(NMe2)4 in the radiation-sensitive coating prior to in situ hydrolysis.

[0026] Fig.11A set of SEM micrographs of five patterned coatings formed from an indicated composition and radiation dose.

[0027] Fig.12 A graph showing the line width roughness (LWR) as a function of dose-to-size for six resist compositions, which were obtained based on patterning 16 nm lines at a 32 nm pitch under EUV light at a wavelength of 13.5 nm and the dose-to-size values to achieve a critical dimension of 16 nm.

[0028] Fig.13 A set of EUV contrast graphs as a function of dose for five coatings formed from different amounts of methyl ligands as radiation-sensitive groups.

[0029] Fig.14 A set of graphs showing the aerial critical dimension as a function of radiation dose for coatings with three different amounts of methyl ligands.

[0030] Fig.15 A set of three SEM micrographs of patterns formed by different EUV radiation doses. Detailed Description

[0031] Improved patterning performance at lower radiation doses can be obtained using an organotin patterning composition having a selected ratio of radiation-sensitive alkyl-Sn bonds and / or a selected amount of a tin precursor without a radiation-sensitive ligand, and improved processing of the radiation-patternable coating can be achieved using in-situ solvent decomposition (e.g., hydrolysis) of the precursor composition. The radiation-patternable coating generally comprises R z SnO (2-(z / 2)-(x / 2)) (OH) x compositions, where 0 < z ≤ 2 and 0 < (z + x) < 4, and R is a radiation-sensitive alkyl ligand, which can exhibit improved low-dose radiation patterning in some embodiments when formed from a selected amount of SnX4 precursor compound to modify the z value of the overall composition. Using in-situ hydrolysis allows for the effective use of the precursor composition through solution-based processing, which would be difficult or impossible to achieve by directly dissolving and depositing an alkyltin oxo-hydroxy composition. As described herein, improved processing to form a patternable R z SnO (2-(z / 2)-(x / 2)) (OH) x composition is achieved by in-situ solvent decomposition. As an alternative to solution-based processing, chemical vapor deposition can be applicable for depositing certain precursor coatings to form an organotin oxide hydroxide precursor. The patterning composition is particularly suitable for EUV patterning at reduced doses and can achieve low line width roughness for smaller features.

[0032] Photoresists having the general formula R have been found to be useful as patterning materials (commonly referred to as photoresists) when deposited as relatively thin coatings and exposed to ultraviolet (UV), extreme ultraviolet (EUV), or electron beam radiation and developed with a suitable solvent. z SnO (2-(z / 2)-(x / 2)) (OH) x (where 0<(x+z)<4 and z>0) provides excellent performance. The foregoing operation has shown that the organotin oxide hydroxide can provide a basis for the formation of a stable precursor solution that can form a resist layer that provides good radiation absorption and development rate contrast. The organotin composition is effectively used as a negative resist or a positive resist. The effect of compounds for EUV and electron beam resists is described in U.S. Patent 9,310,684B2, entitled "Organometallic Solution Based High Resolution Patterning Compositions", by Meyers et al., which is incorporated herein by reference. Based on the current synthesis method, it seems appropriate to extend these compounds to a value of (x+z)=4 so that 0<(x+z)≤4. Improved patterning properties of branched alkyl ligands and blends with alkyl tin oxide hydroxide compositions were discovered and described in published U.S. Patent Application 2016 / 0116839A1, entitled “Organometallic Solution Based High Resolution Patterning Compositions and Corresponding Methods,” to Meyers et al. (hereinafter the '839 Application), which is incorporated herein by reference.

[0033] The above references describe the deposition of organotin oxide hydroxide photoresist films from a coating precursor solution containing R z SnO (2-(z / 2)-(x / 2)) (OH) x The composition is prepared by pre-hydrolyzing one or more R n S X (4-n)The present invention relates to a method for preparing a soluble resist precursor solution from an organotin oxide hydroxide precursor composition (where n=1 or 2), isolating and purifying the organotin hydrolyzate, and dissolving the oxide hydroxide in a suitable solvent or mixture thereof. However, the dissolution and coating of the pre-hydrolyzed organotin oxide hydroxide may have substantial limitations on the achievable ligand recognition and stoichiometry required by avoiding the poor solubility of one or more hydrolyzates, as well as the complex hydrolysis process for some embodiments with the potential for the introduction of unsuitable contaminants. Furthermore, even if a soluble resist precursor solution can be prepared from the organotin oxide hydroxide precursor composition, undesirable solvents may be required or the film morphology may be compromised.

[0034] It has been found that the above mentioned compounds can be prepared by preparing a mixture of one or more suitable R n S X (4-n) Compounds to overcome these limitations, wherein X is a ligand having a hydrolyzable Sn-X bond. n S X (4-n) If sufficiently reactive with water vapor, it can undergo in-situ-MX hydrolysis and condense in the presence of water to produce the corresponding oxide hydroxide as illustrated in the following general reaction:

[0035] R n S X x +x H2O→R n Sn(OH) x +x HX

[0036] R n Sn(OH) x →R n SnO (2-(n / 2)-(x / 2)) OH x +(x / 2)H2O

[0037] where (0<(x+z)≤4). Therefore, by using n S X (4-n) The coating solution of the compound can be used to convert a wide range of R z SnO (2-(z / 2)-(x / 2)) (OH) x The composition is formed into a photoresist coating. In these methods, the R-Sn partial hydrolysis and condensation process is at least partially retained, and the resulting film has MC and MO bonds.

[0038] In one embodiment of the in situ hydrolysis process, the precursor R n S X (4-n)Dissolved in a solvent and directly coated onto a substrate in the presence of water vapor (such as humid air) as appropriate to produce a coating, and then further baked additionally or alternatively in the presence of water vapor to form an organotin oxide hydroxide coating. Thus, water vapor for hydrolysis may be present during coating deposition and / or during a pre-patterning bake step for in-situ hydrolysis. Additionally, by incorporating a variety of R n SnX (4-n) compounds (where n = 0, 1, or 2) (such as SnX4, RSnX'3, R'SnX”3, and R”2SnX2, where R, R', and R” are the same or different and X, X', and X” are the same or different) into a suitable solvent, the selected stoichiometry ranges from 0 < z ≤ 2 and 0 < (x + z) ≤ 4 for R z SnO (2-(z / 2)-(x / 2)) (OH) x thin films can be readily deposited. Similarly, a mixed-ligand hydrolysis product comprising a mixture of organotin oxides R'bSnO (2-(b / 2)-(a / 2)) (OH) a (where 0 < (a + b) < 4 and b > 0) of organotin oxide hydroxide R z SnO (2-(z / 2)-(x / 2) )(OH) x (where 0 < (x + z) < 4 and z > 0) and where R' ≠ R can be prepared in a similar manner by this method. Hydrolyzable R n SnX (4-n) and R' b SnX (4-b) compounds can be dissolved in a common solvent or a mixture of solvents and spin-coated onto a substrate for in-situ hydrolysis. In both cases, the high solubility and rapid hydrolysis of suitable molecular organotin precursor compounds advantageously avoid potential solubility limitations of the target organotin oxide hydroxide hydrolysis products and eliminate the need for complex and sensitive synthetic steps to isolate hydrolyzed and partially condensed resist precursors off-site. In this way, resist precursor preparation can be significantly simplified and the desired compositions with improved properties can be allowed.

[0039] In another embodiment, the relatively high vapor pressure and reactivity of many molecular R n SnX (4-n) compounds enable the use of vapor deposition methods for depositing organotin oxide hydroxide thin film photoresists. Possible deposition methods include, for example, physical vapor deposition (PVD), chemical vapor deposition (CVD), atomic layer deposition (ALD), or variants thereof. For example, one or more gaseous R n SnX (4-n)The compound is introduced into a reaction chamber and reacted with a co-precursor such as H2O or its related decomposition products in the gas phase or on the substrate surface, thereby producing a radiation-sensitive organotin oxide hydroxide coating. If the hydrolyzable compound is deposited on the surface by a subsequent hydrolysis reaction, this process can be regarded as a PVD deposition with in-situ hydrolysis, but if the hydrolysis occurs during the continuous deposition process, it can be regarded as a CVD process. Similarly, if the hydrolyzable precursor is adsorbed, chemisorbed or decomposed sequentially on the substrate surface, and the residual film reacts with a second reactive precursor through multiple deposition / reaction cycles to deposit the corresponding organotin oxide hydroxide, it can be regarded as an ALD process. The advantages of the vapor deposition method can include a reduced resist film defect density, improved thickness and compositional uniformity, and conformal and sidewall coatings of the substrate surface configuration.

[0040] It has been found that the properties of organotin oxide hydroxide photoresists, including, for example, imaging dose, ultimate resolution, and line width roughness (LWR), will depend on the composition of the photoresist coating. For photoresist films having the composition R z SnO (2-(z / 2)-(x / 2)) (OH) x (where 0 < (x + z) ≤ 4 and z > 0), both the identity of the radiation-sensitive ligand R and the R:Sn stoichiometry represented by z are significant variables. Generally, the photoresist film may contain a sufficient amount of the radiation-sensitive ligand R such that the film has a molar concentration ratio of the radiation-sensitive ligand to the metal cation (z) of about 0.1 to about 2. Organotin oxide hydroxide resist films having a ligand ratio within this range can be prepared by pre-hydrolyzing various R n SnX (4-n) precursors (where z = 1 or 2) in appropriate stoichiometry and dissolving the resulting hydrolysis products in a coating solvent subject to solubility and stability limitations. For certain stoichiometries, especially those where 0.1 < z < 1, the photoresist compositions have been found to exhibit favorable photoresist characteristics. However, for photoresist compositions with z < 1, the aforementioned processing limitations can be cumbersome because the solubility of the inorganic SnO (2-(x / 2)) (OH) x hydrolysis product (z = 0) is generally extremely low in organic solvents, outside the range of the extremely limited conditions that help co-hydrolyze and cluster-condense the specific organotin RSnX3 or R2SnX2 moieties. In addition, even when these conditions have been identified and the hydrolysis products have been separated and dissolved, the precursor solution stability, stoichiometry, ligand identity, and solvent can be unfavorably limited relative to the required values for operations such as EUV photoresists.

[0041] These processing and combination limitations can be overcome by rapidly adding a hydrolyzable SnX4 compound directly to a precursor coating solution containing one or more pre-hydrolyzed organotin oxide hydroxides, or one or more RSnX3 and / or R2SnX2 compounds selected to undergo substantially complete hydrolysis and subsequent condensation and volatilization of the HX byproducts on the coating, and baking in the presence of water or another suitable source of oxygen and hydrogen. In this manner, the identification and relative stoichiometry of multiple radiation-sensitive ligands in the precursor coating solution and photoresist film can be independently controlled across a wide range of ligand to metal cation total ratios, subject to relaxed solution stability and solubility constraints and simplified precursor synthesis. Thus, an appropriately selected SnX4 composition can be incorporated into a precursor mixture or process to enable vapor deposition of organotin oxide hydroxides with comparable compositions.

[0042] By relaxing the inherent stability and solubility constraints of organometallic compounds with MC and MO bonds, alternative metal species can also be added to MX' n In the precursor coating solution or reaction gas mixture of the form of, wherein M is a metal cation selected from Group 2 to Group 16 metals, and n is determined by the valence of the metal cation and the charge of the ligand, but is generally 3 to 6. When M≠Sn, the X' ligand can be used with R in the same formulation n S X (4-n) The X's in the compounds are identical or different. In both cases, these ligands and MX' n Depending on similar conditions; rapid and essentially complete hydrolysis in the presence of H2O and diffusion and volatilization of X(X') ligand hydrolysis products from the oxide hydroxide film. Substituted metal cations incorporated into organotin oxide hydroxide coatings in this manner can be useful for tuning radiation absorption, film density, thermal decomposition of metal ligands, development rate with preferred developers, or other desired photoresist properties.

[0043] Previously, the identity and relative stoichiometry of multiple R-Sn moieties present in an organotin oxide hydroxide resist film have been provided to afford improved patterning performance as described in the '839 application. Although at least in part the branched alkyl ligands and related blend compositions described herein can be obtained using pre-hydrolyzed organotin oxide hydroxide compounds dissolved in a solvent, significant limitations regarding ligand identity and stoichiometry have been found in the context of practical processes suitable for commercial use. Many of these limitations are associated with the solubility of the hydrolysis products. Although some mono-organotin hydrolysis products (such as n-butyltin oxide hydroxide) have excellent solubility in a wide range of organic solvents, it is difficult to regenerate and / or control the hydrolysis products of mono-tert-butyltin moieties which generally do not dissolve sufficiently in useful solvents and / or at the desired solution concentrations (e.g., t BuSnO (3 / 2-(x / 2)) (OH) x , where (0 < x < 3)). As demonstrated in the '839 application, although it is possible to prepare a t BuSnO (3 / 2-(x / 2)) (OH) x solution using methanol and solvent blends derived therefrom, the volatility, flash point, and toxicity of methanol render it unsuitable as the desired solvent for semiconductor manufacturing. Additionally, the lower maximum concentration limits the range of film thicknesses achievable and the composition of possible blend precursor formulations and coatings. These limitations are avoided in the examples below, where high-performance t BuSn(NEt2)3 in 4-methyl-2-pentanol is spin-coated in the presence of water vapor to demonstrate t BuSnO (3 / 2-(x / 2)) (OH) x photoresist films.

[0044] Similarly, the lower solubility of the hydrolysis products of mono-methyltin moieties (e.g., MeSnO (2-(z / 2)-(x / 2)) (OH) x ) limits the film thickness and composition range of the formulations and coatings. However, by preparing a resist precursor solution containing an MeSnX3 compound that is readily hydrolyzable and highly soluble, a resist film containing the resulting methyl-tin oxide hydroxide in a blend formulation having t BuSnO (3 / 2-(x / 2)) (OH) x has been deposited and found to provide superior lithographic performance. Significantly, using the methods and precursor solutions disclosed herein, the resist precursor solution solvent limitations are substantially relaxed, and the resist film stoichiometry can be more readily adjusted to achieve suitable lithographic characteristics. Thus, by mixing multiple hydrolyzable organotin compounds R n SnX(4-n) +R' z SnX' (4-z) +R” a SnX” (4-a) +... (where 0≤(n, z, a)≤2 and at least one of n, z, a, etc.>0) to obtain the desired photoresist precursor solution and a subsequent thin film composition comprising a mixture of an organic tin portion (which has organic ligands (R, R', R", etc.) in a wide range of molar ratios with respect to each other) and a metal cation.

[0045] Alternatively, the selected R n S X (4-n) Compounds (where n = 0, 1 or 2) are added to a precursor coating solution containing one or more independently synthesized organotin oxide hydroxide hydrolyzates dissolved in a suitable solvent. n S X (4-n) The compound can hydrolyze upon exposure to water vapor or hydroxide moieties, thereby condensing with the starting organotin oxide hydroxide during the coating and baking steps to form a coating having an alkyl ligand to metal ratio initially determined by the stoichiometry of the precursor compounds in the precursor coating solution.

[0046] The selection of ligands (X) having hydrolyzable Sn-X bonds in the aforementioned compounds is important for the effectiveness of solubilization, coating, and successful in situ hydrolysis. Suitable ligands should form stable bonds with Sn in the absence of Lewis acids and are generally substances that react quickly with acidic protons to produce substances that are easily desorbed or volatilized from the condensed oxide hydroxide film, thereby reducing voids, regional separations, or other inhomogeneities. For R n S X (4-n) For compounds, X may be a single unique ligand, however, in certain embodiments, it may refer to a combination of multiple different ligands, such as R n S X 1 a X 2 b X 3 c X 4 d , where a+b+c+dn=4, and 0≤n≤2. Examples of compounds of this type are: t BuSn(NEt2)2(O t Bu) t BuSn(NEt2)(NH2)(O t Bu)、 t BuSn(NEt2)(O t Bu)2、MeSn(NEt2)(Ot Bu)2、MeSn(NEt2)2(O t Bu)、( t Bu)2Sn(NEt2)(O t Bu), Me2Sn(NEt2)(O t Bu)、(Me)( t Bu)Sn(NEt2)2、(Me)( t Bu)Sn(NEt2)(O t Bu)、( i Pr)( t Bu)Sn(NMe2)(O t Bu) and mixtures thereof.

[0047] The choice of -X ligand can be determined in part by the identity of the hydrocarbyl ligand R, other hydrolyzable ligands, and the stoichiometric ratio (R:Sn), since the reactivity of a given Sn-X moiety with respect to hydrolysis or solvolysis will be modified by the overall ligand environment around the metal in terms of both steric (kinetic) and electrostatic (thermodynamic) effects.

[0048] It has been found that one or more R n S X (4-n) Formulations of compounds where -X is a short chain aliphatic dialkylamide -NR'2 or alkoxide -OR' ligand where R' contains <10 carbon atoms are particularly useful for these applications. When exposed to atmospheric moisture during the coating and baking process, these materials rapidly hydrolyze and condense with other organotin precursor components as described above, liberating volatile dialkylamines and alcohols and forming organotin oxide hydroxides with excellent photoresist properties. Other suitable ligands of this type include: amido, alkylamido, dialkylamido, alkoxo, aryloxo, azido, imide, and others known to those skilled in the art.

[0049] In some embodiments, for example, the organotin dialkylamide is dissolved in a protic solvent such as an alcohol and the tin precursor compound can react with the solvent. When the solvent is an alcohol or similar reactant, complete or partial ligand metathesis can occur by solvent decomposition such as alcoholysis as illustrated in the following reaction.

[0050] R n Sn(NR'2) (4-n) +(4-n)R”OH→R n Sn(OR”) (4-n) +(4-n)HNR'2. (2)

[0051] If the product tin species (such as tin(IV) alkoxide, Rn Sn(OR”) (4-n) ) possesses the necessary properties with respect to water reactivity, hydrolysis byproduct volatility, diffusivity, and other properties discussed herein to produce a suitable oxide hydroxide film after coating and baking in an appropriately humid environment, then such solvolysis and metathesis reactions in Reaction Scheme 2 are expected and acceptable and potentially even beneficial.

[0052] The improved precursors described herein open up more possibilities for the composition of patternable coatings based on rational coating solutions and in-situ hydrolysis. In-situ hydrolysis provides the ability to be a suitable alternative to a range of vapor deposition methods based on processed solutions. By this ability to tailor the composition of patternable coatings with radiation sensitive ligands, improved patterning with lower radiation dose and good pattern quality has been achieved.

[0053] Precursor composition

[0054] Precursor compositions for forming resist coatings typically include tin cations having suitable radiation-sensitive hydrocarbon-based stabilizing ligands and additional ligands having hydrolyzable Sn bonds selected for processing. For processing into patternable coatings, the precursor composition is typically formed into a solution with a solvent, and an organic solvent can typically be formed into a coating by solution coating or a vapor-based deposition process. The final resist coating is based on the chemical reaction of metal oxides, and the precursor solution of tin cations with alkyl ligands provides a stable solution with good resist properties. The ligands of the precursor solution are typically selected to facilitate solution formation and related processing functions. As mentioned above, a precursor composition with a ligand that can hydrolyze Sn bonds can be introduced into the precursor solution to improve the range of compositions that can be formed into a stable solution, which is expected to be subsequently hydrolyzed to provide an organic tin oxide hydroxide material for a patternable coating. It has been found that compositions with blends of alkyl ligands (typically with at least one branched alkyl ligand) provide the desired patterning properties.

[0055] Alkyl ligands provide radiation sensitivity, and the specific choice of ligand and stoichiometry relative to the metal can affect the radiation sensitivity. In addition, the precursor solution can be designed to achieve a desired radiation absorption level for a selected radiation energy based on the choice of metal cation and associated ligand. Although the above discussion outlines the important details of the range of precursor compositions suitable for the improved processing described herein, more details are presented on the use of alkyltin amide / alkoxy precursor compositions for in situ hydrolysis. As mentioned above, various compounds are described that can provide improved solubility in the desired solvents and good processability for radiation-sensitive coatings. A wide range of precursor modifications may be made by involving a new class of precursors with at least some in situ hydrolysis of some steam hydrolysis / oxidation reactants to form radiation-patternable coatings.

[0056] Generally speaking, the precursor solution may include:

[0057] a1 1 z1 SnO (3 / 2-z1 / 2-x1 / 2) (OH) x1 +a2 R 2 z2 SnO (3 / 2-z2 / 2-x2 / 2) (OH) x2 +...+b1 R 1 ' y1 S X 1 4-y1 +b2R 2 ' y2 S X 2 4-y2 +...+c1SnX 1 '4+c2SnX 2 '4+...+d1M 1 X 1 ” n1 、d2M 2 X 2 ” n2 +..., (1)

[0058] Where a1+a2+...+b1+b2+...+c1+c2+...+d1+d2+...=1, that is, these parameters correspond to the molar fraction of the metal in the precursor composition in the solution, (0≤(a1, a2, ...)≤0.99), (0≤(b1, b2, ...)≤1), (0≤(c1, c2, ...)≤0.6), (0≤(d1, d2, ...)≤0.5), where 0.01<(b1+b2+...+c1+c2+...), R( R1 , R 2 , …) and R'(R 1'、R 2 ', ...) are independently hydrocarbon groups or a combination thereof, X(X 1 , X 2 、...)、X'(X 1 ', X 2 ', ...) and X”(X 1 ”'、X 2 ”, …) are independently ligands having hydrolyzable bonds to the relevant metal or a combination thereof, M 1 、M 2 , ... are non-tin metal ions, (0<(x1, x2, ...)<3), (0<(z1, z2, ...)≤2), (1<(y1, y2, ...)≤3), and n1, n2, ... are non-tin metal ions. 1 、M 2 、...valence of ions and X 1 ”、X 2 "…is determined by the charge on the metal. Generally, M is a metal of Group 2 to Group 16, and for many metals, n ranges from 2 to 6. Desirable metals for M may include Hf, Zr, W, Ta, Co, Ni, In, Sb, Bi, Te or others. Representative suitable ML" n Compounds include, for example, Zr(OtBu)4, Hf(NMe)4, In(O iIn some embodiments, all "a" parameter values ​​are zero, so that all ligands are hydrolyzed in situ. In other embodiments, 0.1≤(a1, a2, ...)≤0.90, or 0.2≤(a1, a2, ...)≤0.85, or 0.25≤(a1, a2, ...)≤0.75. In some embodiments, 0.25≤(b1, b2, ...)≤1, or 0.3≤(b1, b2, ...)≤0.95, or 0.35≤(b1, b2, ...)≤0.9. In additional embodiments, 0≤(c1, c2, ...)≤0.4 or 0.025≤(c1, c2, ...)≤0.4 or 0.05≤(c1, c2, ...)≤0.35 or 0.1≤(c1, c2, ...)≤0.3, and 0≤(d1, d2, ...)≤0.5 or 0.025≤(d1, d2, ...)≤0.4 or 0.05≤(d1, d2, ...)≤0.3. Those skilled in the art will recognize that additional ranges of "a", "b", "c" and "d" parameters within the above-defined ranges of the present invention are encompassed and within the present invention. As used herein, the symbols "<" and "≤" implicitly carry the concept of the corresponding range limits as "about" the specified values ​​within experimental error.

[0059] In summary, the precursor composition may include one or more compounds, at least one of which has a ligand that hydrolyzes the metal bond and one or more of which have a hydrocarbyl ligand to provide radiation sensitivity. The composition is typically modified to be processable with a suitable organic solvent to form a precursor solution as described in the following section. The precursor is typically modified to provide the desired patterning properties as well as good processability.

[0060] In some embodiments, the precursor composition may include two organotin compounds with different hydrocarbyl ligands, three organotin compounds with different hydrocarbyl ligands, or a mixture of more than three organotin compounds with different hydrocarbyl ligands. In addition, the precursor composition may include a mixture of compounds without metal-carbon bonds and one or more compounds with radiation-sensitive alkyl ligands with metal-carbon bonds. Typically, for the second or third mixture, the mixture includes at least about 5 mole percent of each component with a different hydrocarbyl ligand, in some embodiments at least about 10 mole percent, and in other embodiments at least about 20 mole percent of each component with a different hydrocarbyl ligand. Those skilled in the art will recognize that additional ranges of mole percentages of the components within the above explicit ranges are encompassed and within the present invention.

[0061] In some embodiments, the precursor composition comprises an R-Sn moiety having a hydrocarbyl ligand and an inorganic metal SnX4 or MX n Typically, these mixtures contain at least about 0.5 mole percent of each metal component, in some embodiments at least about 5 mole percent, and in other embodiments at least about 10 mole percent of each component. Those skilled in the art will recognize that additional ranges of mixture components within the above explicit ranges are contemplated and within the present invention. The components of the precursor composition can be incorporated into a solution and not separately formed into a solid blend prior to, for example, forming a coating.

[0062] Whether one or more different hydrocarbyl ligands are present, the R groups can be straight chain, branched (i.e., secondary or tertiary carbon atoms to which the metal is attached), or cyclic hydrocarbyl groups. Each R group typically independently has from 1 to 31 carbon atoms, with 3 to 31 carbon atoms for bonded secondary carbon atoms and 4 to 31 carbon atoms for bonded tertiary carbon atoms, for example, methyl, ethyl, propyl, butyl, and branched alkyl groups. Specifically, when a compound can be represented by R in another representation 1 R 2 R 3 When CSnX3 is represented, a branched alkyl ligand is desired, wherein R 1 and R 2 are independently alkyl groups having 1 to 10 carbon atoms, and R 3 is hydrogen or an alkyl group having 1 to 10 carbon atoms. 1 and R 2 can form a cycloalkyl moiety, and R 3 Other groups in the ring part may also be attached. Suitable branched alkyl ligands may be, for example, isopropyl (R 1 and R 2 is methyl and R 3 is hydrogen), tert-butyl (R 1 , R 2 and R 3 is methyl), tert-amyl (R 1 and R 2 is methyl and R 3 -CHCH3), sec-butyl (R 1 Methyl, R 2 is -CHCH3 and R 3is hydrogen), cyclohexyl, cyclopentyl, cyclobutyl and cyclopropyl. Examples of suitable cyclic groups include, for example, 1-adamantyl (-C(CH2)3(CH)3(CH2)3 or tricyclo(3.3.1.13,7)decane bonded to the metal at the tertiary carbon) and 2-adamantyl (-CH(CH)2(CH2)4(CH)2(CH2) or tricyclo(3.3.1.13,7)decane bonded to the metal at the secondary carbon. In other embodiments, the hydrocarbon group may include an aryl or alkenyl group, such as benzyl, allyl, or alkynyl. In other embodiments, the hydrocarbon ligand R may include any group consisting solely of C and H and containing 1 to 31 carbon atoms. For example: a straight or branched alkyl group ( i Pr, t Bu, Me, n Bu), cycloalkyl (cyclopropyl, cyclobutyl, cyclopentyl), alkene (alkenyl, aryl, allyl) or alkynyl or a combination thereof. In other embodiments, suitable R-groups may include hydrocarbon groups substituted by heteroatom functional groups (including cyano, thio, silane, ether, ketone, ester or halogenated groups or a combination thereof).

[0063] Some suitable metal compositions with the desired ligand structure are available from commercial sources such as Alfa Aesar (MA, USA) and TCI America (OR, USA), and other metal ligand compositions can be synthesized as described below. The methods described herein can be used to synthesize low metal contaminant precursor compositions based on the use of appropriately low contaminant starting materials and appropriate purification.

[0064] The desired patterning results are obtained using precursor compounds with branched alkyl ligands. However, more comprehensive advantages of ligand selection have been achieved by using mixed alkyl ligands because individual favorable patterning properties imparted by different ligands (such as dose and line width roughness) can be obtained by blending multiple alkyl ligands as illustrated in the examples provided by the teachings herein. Processing with in-situ hydrolyzed precursors provides for the efficient use of methyl ligands in the desired solvent-based precursor solution. Effective patterning of mixtures with tert-butyl ligands and methyl ligands and hydrolyzable compounds containing tert-butyl ligands and hydrolyzable SnX4 compounds (X = NMe2 or X = O t Precursors of mixtures of: Bu) are described in the examples below.

[0065] It has been found that for mixtures of precursor compounds having different alkyl ligands based on the radiation doses of the corresponding individual precursor compounds, the amount of radiation cure can be scaled approximately linearly. Due to the lower radiation doses that can be used with branched alkyl ligands, it is generally desirable for the mixture to include at least one branched organic ligand. However, correspondingly, it has been found that LWR can be improved with mixtures of precursor compounds having different organic ligands. While not wishing to be bound by theory, it is possible that the improved LWR values ​​observed for the mixture composition can be attributed to the enhanced etching for the mixture composition without a significant reduction in contrast in the pattern. In this case, the observations can be extended to mixture compositions containing combinations of organotin compounds carrying branched or unbranched alkyl groups.

[0066] The X, X' and X" ligands are generally Lewis bases that react appropriately with acidic protons of water or other Lewis acids to form volatile products by hydrolysis or solvolysis of the MX, M-X' and MX" bonds. Alternatively, these ligands can react with suitable reactants to form volatile products by oxidation or reduction reactions. The ligands can generally be identified by the acid dissociation constant (pK) of their conjugate acids. a ) are classified into the following categories, wherein the desired ligand of some embodiments has a conjugate acid pK greater than about 4 a Thus, X, X' and X" typically comprise atoms bound to a metal (e.g., tin) that can undergo nucleophilic substitution involving H2O and -OH. The resulting M-OH or M-OH2 ligands can then react via subsequent condensation or dehydration steps to form oxide hydroxide networks.

[0067] Suitable ligands include: alkylamide or dialkylamide (-NR 1 R 2 , where R 1 and R 2 are independently a hydrocarbon group having 1 to 10 carbon atoms or hydrogen); siloxo (-OSiR 1 R 2 R 3 , where R 1 , R 2 independently a hydrocarbon group having 1 to 10 carbon atoms); a silylamide group (-N(SiR 1 3)(R 2 ), where R 1 and R 2 independently a hydrocarbon group having 1 to 10 carbon atoms); a disilylamide group (-N(SiR 1 3)(SiR 2 3), where R 1 and R 2independently a hydrocarbon group having 1 to 10 carbon atoms); alkyloxy and aryloxy (-OR, wherein R is an alkyl or aryl group having 1 to 10 carbon atoms); azido (-N3); alkynyl (-C≡CR, wherein R is a hydrocarbon group having 1 to 9 carbon atoms); amide (-NR 1 (COR 2 ), where R 1 and R 2 are independently a hydrocarbon group having 1 to 7 carbon atoms or hydrogen); an amidino group (-NR 1 C(NR 2 )R 3 ), where R 1 and R 2 are independently a hydrocarbon group having 1 to 8 carbon atoms or hydrogen); an imine group (-N(COR 1 )(COR 2 ), where R 1 and R 2 is independently a hydrocarbyl group having 1 to 8 carbon atoms or hydrogen) or a fluorinated analog thereof.

[0068] The metal in an inorganic or organometallic material can significantly affect the absorption of radiation. Tin provides strong absorption of extreme ultraviolet light at 13.5 nm. In combination with alkyl ligands, the metal also provides strong absorption of ultraviolet light at a wavelength of 193 nm. Tin also provides good absorption of electron beam radiation. The absorbed energy is regulated by metal organic interactions, which can lead to severing of metal ligand bonds and desired control of material properties. Nevertheless, other metal compositions can be introduced to further affect the absorption characteristics and overall resist performance. As mentioned above, MXene is typically introduced. n Other non-tin metals, wherein X is a ligand having a hydrolyzable metal bond.

[0069] The use of precursor compounds having ligands with hydrolyzable metal bonds can simplify the preparation of precursor solutions because in situ hydrolysis avoids the many synthesis and separation steps required to produce defined hydrolysis products. Specifically, solution phase hydrolysis and subsequent condensation and separation of organotin oxide hydroxide hydrolysis products can involve significant solubility changes during the reaction, allowing the avoidance of solution-based steps to bypass potentially difficult process steps. To the extent that the ingredients of the precursor composition include separately hydrolyzed components, the particular components can be obtained using solution-based hydrolysis, such as using a base-catalyzed aqueous solution, as described in the '839 application. Components having ligands with hydrolyzable metal bonds can generally be purchased or synthesized from suitable starting materials (e.g., from tin halide compositions or tetrakis(dialkylamido)tin compositions), as described in the Examples.

[0070] Precursor solution formation and coating properties

[0071] A range of precursor solutions can be prepared based on the compositions described in the preceding sections. Precursor compositions generally have the commonality of involving some degree of hydrolysis-sensitive metal-ligand bonding. For precursor compounds with sufficient vapor pressure, hydrolysis can alternatively be performed in situ in the coating or as part of the vapor deposition process. Precursor solutions for solution deposition generally contain tin cations and one or more non-tin metal cations in an optionally selected organic solvent.

[0072] The concentration of the ligand-stabilized metal cation in the solution can be selected to provide suitable solution characteristics for a particular solution deposition method, such as spin coating, slot coating, dip coating, spray or mist coating or printing, and designed to form a coating composition after removal of at least a portion of the solvent and a final inorganic solid dominated by tin oxide after radiation and / or heat treatment, exposure to plasma or the like.

[0073] With precursor solutions based on alkyl stabilized ligands and organic solvents, the progress of oxidation can be controlled as part of a procedure for first processing the solution into a coating material and then processing into a final metal oxide composition with organic ligands by hydrolysis and condensation of the reactants with ambient water vapor during coating and / or hydrolysis and condensation after coating. As described herein, alkyl ligands, particularly branched alkyl ligands and / or combinations of alkyl ligands in specific stoichiometric amounts relative to the metal, can be used to provide significant control over processing the solution into an effective radiation resist composition. Processing with alcohol-based solvents can involve partial or complete substitution of the alkoxy ligand with an alcohol of the starting ligand having a hydrolyzable metal bond, but such substitution may not alter subsequent processing in any significant manner.

[0074] The precursor solution concentration may be suitably specified based on the molar concentration of tin ions and the concentration of any other metal that may be specified accordingly by the mole fraction value of the metal relative to tin. Generally, the precursor solution comprises about 0.005M to about 1.4M tin cations, in further embodiments about 0.02M to about 1.2M, and in additional embodiments about 0.1M to about 1.0M tin cations. The total non-tin metal in the precursor solution may typically be in the range of about 0.025 mol % to about 10 mol % of the total metal ions, and in further embodiments about 10 mol % to about 50 mol % of the total metal ions. Those skilled in the art will recognize that additional ranges of tin cations within the above explicit ranges are encompassed and within the present invention.

[0075] In general, the desired hydrolyzate compound can be dissolved in an organic solvent, for example, alcohols, aromatic and aliphatic hydrocarbons, esters or combinations thereof. Specifically, suitable solvents include, for example, aromatic compounds (e.g., xylene, toluene), ethers (anisole, tetrahydrofuran), esters (propylene glycol monomethyl ether acetate, ethyl acetate, ethyl lactate), alcohols (e.g., 4-methyl-2-propanol, 1-butanol, methanol, isopropanol, 1-propanol), ketones (e.g., methyl ethyl ketone), mixtures thereof, and the like. In general, the choice of organic solvent can be affected by the solubility parameters, volatility, flammability, toxicity, viscosity and possible chemical interactions of other processing materials. After dissolving and combining the components of the solution, the characteristics of the material may change due to partial in-situ hydrolysis, hydration and / or condensation. When referring to the composition of the solution in this article, reference is made to the components added to the solution, since complex formulations may undergo solvolysis and ligand metathesis, or may produce metal polynuclear materials in the solution that may not be well characterized. For certain applications, it is desirable for the organic solvent to have a flash point of no less than about 10° C., in further embodiments no less than about 20° C., and in further embodiments no less than about 25° C., and a vapor pressure of no more than about 10 kPa, in some embodiments no more than about 8 kPa, and in further embodiments no more than about 6 kPa at 20° C. Those skilled in the art will recognize that additional ranges of flash points and vapor pressures within the explicit ranges above are contemplated and within the invention.

[0076] The concentration of the substance in the precursor solution can be selected to achieve the desired physical properties of the solution. Specifically, lower concentrations can generally lead to desired properties of the solution for certain coating methods such as spin coating, which can achieve thinner coatings using reasonable coating parameters. It may be desirable to use thinner coatings to achieve ultra-fine patterning and to reduce material costs. In general, the concentration can be selected to make it suitable for the selected coating method. The coating properties are further described below.

[0077] In general, the precursor solutions can be preferably mixed using a suitable mixing device suitable for the volume of the material being formed. Suitable filtration can be used to remove any contaminants or other components that are not properly dissolved. In some embodiments, it may be desirable to form separate solutions that can be combined to form a precursor solution. Specifically, separate solutions comprising one or more of the compounds indicated in formula (1) above can be formed. In general, separate solutions or combined solutions can be well mixed. The resulting solution can be referred to as a stable metal cation solution.

[0078] The stability of the precursor solution can be evaluated relative to the changes associated with the starting solution. Specifically, if phase separation occurs with the generation of larger solvent particles or if the solution loses its ability to form the desired pattern, the solution has lost stability. Based on the improved stabilization method described herein, the solution can be stabilized for at least about one week, at least about 2 weeks in other embodiments, and at least about 4 weeks in other embodiments without additional mixing. Those skilled in the art will recognize that additional ranges of stable time are covered and within the present invention. Suitable solutions with sufficient stable time can usually be prepared so that the solution can be commercially released as having a suitable shelf life.

[0079] As described herein, a treatment method for reducing metal contamination has been developed. Therefore, a precursor solution with extremely low content of non-tin metal can be prepared. In general, all unintentional metal concentrations can be reduced to values ​​of no more than about 1 part per million (ppm) by weight, no more than about 200 parts per billion (ppb) by weight in other embodiments, no more than about 50 ppb in additional embodiments, and no more than about 10 ppb in other embodiments. In some embodiments, it may be necessary to add other metal elements to affect the treatment, and these elements can generally be determined by a content of at least about 1 weight percent and at least about 2 weight percent in some embodiments, and thus can be distinguished from contaminant metals (if appropriate). Specifically, metal contaminants to be reduced include alkali metals and alkaline earth metals, Au, Ag, Cu, Fe, Pd, Pt, Co, Mn and Ni. Those skilled in the art will recognize that additional ranges of metal content within the above-mentioned explicit content are covered and within the present invention.

[0080] The foregoing efforts to produce precursor solutions and coatings with low levels of metal contaminants are described in the '839 application. The use of water vapor for hydrolysis provides hydrolysis reactants that are substantially free of metal contaminants, which can further be effective in forming low-contaminant patternable coatings based on low-contaminant tin compositions. Suitable starting materials with low levels of metal contaminants can be obtained commercially or by purification.

[0081] Coating treatment and in-situ hydrolysis

[0082] The coating material can be formed by depositing and then treating the precursor solution onto the selected substrate. Using the precursor solution described herein, some hydrolysis and condensation are usually performed during coating, and the subsequent processing steps such as heating in air are completed or further post-coating. The substrate usually has a surface on which the coating material can be deposited, and the substrate can include multiple layers, wherein the surface is related to the uppermost layer. In certain embodiments, the substrate surface can be processed to prepare a surface for adhering the coating material. In addition, the surface can be cleaned and / or leveled when appropriate. Suitable substrate surfaces can include any reasonable material. Some substrates that have received much attention include, for example, silicon wafers, silicon dioxide substrates, other inorganic materials (such as ceramic materials), polymer substrates (such as organic polymers), their composites and combinations thereof across the surface and / or in the layer of the substrate. Although any reasonable forming structure can be used, a wafer such as a relatively thin cylindrical structure can be suitable. For certain applications based on their low cost and flexibility, polymer substrates on non-polymer structures or substrates with polymer layers will be desired, and suitable polymers can be selected based on relatively low processing temperatures that can be used to process the patternable materials described herein. Suitable polymers may include, for example, polycarbonates, polyimides, polyesters, polyolefins, copolymers thereof, and mixtures thereof. In general, substrates with flat surfaces are required, especially for high-resolution applications. However, in particular embodiments, the substrate may have a general surface morphology, wherein the resist coating is intended to fill or planarize the features used for specific patterning applications. Alternatively, using the vapor deposition method described herein, existing surface morphologies and features can be conformally coated with organic tin oxide hydroxide photoresists for specific patterning applications.

[0083] In general, in addition to the vapor deposition processes disclosed herein, any suitable solution coating process may be used to deliver the precursor solution to the substrate. Suitable coating methods may include, for example, spin coating, spray coating, dip coating, knife edge coating, printing methods (such as inkjet printing and screen printing), etc. Although the resolution currently available from printing and the like is significantly lower than the level of resolution available from radiation-based patterning as described herein, some of these coating methods also form a pattern of the coating material during the coating process.

[0084] If radiation is used for patterning, spin coating can be a desired method for relatively uniformly covering the substrate, although there may be edge effects. In some embodiments, the wafer can be rotated at a rate of about 500rpm to about 10,000rpm, about 1000rpm to about 7500rpm in other embodiments, and about 2000rpm to about 6000rpm in other embodiments. The rotation speed can be adjusted to obtain the desired coating thickness. Spin coating for a time of about 5 seconds to about 5 minutes, and about 15 seconds to about 2 minutes in other embodiments can be performed. Initial low-speed rotation (e.g., with 50rpm to 250rpm) can be used to carry out coating of the composition across the starting volume of the substrate. Backside rinsing, edge bead removal steps, etc. can be performed with water or other suitable solvents to remove any edge beads. Those skilled in the art will recognize that the additional range of spin coating parameters within the above-mentioned clear range is covered and within the present invention.

[0085] The coating thickness may generally be a function of the concentration of the precursor solution, the viscosity, and the rotation speed of the spin coating. For other coating processes, the thickness may also be adjusted by selecting coating parameters. In some embodiments, it may be desirable to use a thinner coating to facilitate the formation of smaller and highly resolved features in subsequent patterning processes. For example, the dried coating material may have an average thickness of no more than about 10 microns, no more than about 1 micron in other embodiments, no more than about 250 nanometers (nm) in other embodiments, about 1 nanometer (nm) to about 50nm in additional embodiments, about 2nm to about 40nm in other embodiments, and about 3nm to about 25nm in some embodiments. Those skilled in the art will recognize that additional ranges of thickness within the above-defined ranges are encompassed and within the present invention. Non-contact methods of x-ray reflection and / or ellipsometry based on the optical properties of the film may be used to assess the thickness. In general, the coating is relatively uniform to facilitate processing. In some embodiments, the variation in coating thickness does not exceed ±50% of the average coating thickness, does not exceed ±40% in other embodiments, and does not exceed about ±25% relative to the average coating thickness in other embodiments. In some embodiments, such as high uniformity coatings on larger substrates, the evaluation of coating uniformity may be evaluated with a 1 cm edge exclusion, i.e., the coating uniformity is not evaluated for the portion of the coating within the 1 cm edge. Those skilled in the art will recognize that additional ranges within the explicit ranges above are contemplated and within the present invention.

[0086] The coating process itself may result in evaporation of some of the solvent, since many coating processes form droplets or other forms of coating material having a large surface area and / or stimulate movement of the evaporating solution. As the concentration of the substance in the material increases, the loss of solvent is intended to increase the viscosity of the coating material. The goal during the coating process may be to remove enough solvent to stabilize the coating material for further processing. The reactive species may condense during coating or subsequent heating to form a hydrolyzate coating material.

[0087] Generally, prior to radiation exposure, the coating material may be exposed and optionally heated in the presence of atmospheric moisture to hydrolyze hydrolyzable metal bonds in the precursor composition, and / or further drive off solvent and promote densification of the coating material. The coating material after in situ hydrolysis may generally form a polymeric metal oxo-hydroxy network based on the binding of oxo-hydroxy ligands to the metal, wherein the metal also has some alkyl ligands or a molecular solid composed of a polynuclear metal oxo / hydroxy species having alkyl ligands.

[0088] The hydrolysis / solvent removal process may or may not be quantitatively controlled relative to the precise stoichiometry of the heated coating material and / or the specific amount of residual solvent in the coating material. In addition, the formulations and compositions expressed herein may contain some additional water, whether directly bonded to Sn or as a hydrogen bond to the network structure of Sn. Experimental evaluation of the resulting coating material properties can generally be performed to select treatment conditions that are effective for the patterning process. Although the successful application of the process may not require heating, heating the coated substrate to accelerate the process and / or increase the reproducibility of the process and / or promote the gasification of hydrolysis byproducts (such as amines and or alcohols) may be required. In embodiments where heating is applied to remove solvents, the coating material may be heated to a temperature of about 45°C to about 250°C, and in other embodiments to a temperature of about 55°C to about 225°C. Heating for solvent removal may generally be performed for at least about 0.1 minutes, about 0.5 minutes to about 30 minutes in other embodiments, and about 0.75 minutes to about 10 minutes in additional embodiments. Those skilled in the art will recognize that additional ranges of heating temperatures and times within the above-defined ranges are encompassed and within the present invention. As a result of thermally treating, hydrolyzing, and densifying the coating material, the coating material may exhibit an increase in refractive index and radiation absorption without significant loss of contrast.

[0089] Vapor-based coating formation

[0090] The development of precursor compounds containing R groups having substantially non-hydrolyzable Sn bonds and X ligands having hydrolyzable Sn bonds was developed for the development of vapor deposition of radiation-patternable organotin oxide hydroxide coatings. Specifically, relatively high vapor pressures and a number of R groups such as those listed in Table 1 n S X (4-n)The reactivity of the compounds makes it possible to use vapor deposition methods for depositing organotin oxide hydroxide thin film photoresists. Hydrolysis can be carried out as part of the deposition process by introducing a hydrolyzable precursor in the vapor phase into a closed reactor at ambient atmospheric pressure, i.e., chemical vapor deposition. Possible vapor deposition methods include chemical vapor deposition (CVD), atomic layer deposition (ALD), and their variations, many of which have been used to deposit inorganic metal oxide and nitride films with metal alkylamide, alkoxide, and halide precursors, [1 to 4] including SnO2 from SSn(NMe2)4. [5]. For vapor deposition, one or more metal-containing precursors are typically reacted or reacted multiple times with a small molecule vapor phase reagent such as H2O, H2O2, O3, O2, or CH3OH, which acts as a source of O and H for producing oxides and oxide hydroxides. If desired, physical vapor deposition methods can also be performed where a precursor composition having ligands with hydrolyzable Sn bonds is deposited from the vapor phase after coating formation and these bonds are subsequently hydrolyzed, but for vapor phase processing, hydrolysis / oxidation during deposition can generally be more efficient.

[0091] Table 1

[0092] Compound Vapor pressure (Torr) Temperature(℃) <![CDATA[ t BuSn(NEt2)3]]> 0.3 95 <![CDATA[ t BuSn(NMe2)3]]> 0.3 55 <![CDATA[ t This is Sn(O t This)3]]> 3.5 ~82 <![CDATA[ i PrSn(NMe2)3]]> 1.4 53 <![CDATA[Sn(NEt2)4]]> 0.5 110 <![CDATA[Sn(NMe2)4]]> 0.1 ~54 <![CDATA[Sn(O t This)4]]> 0.3 65 <![CDATA[Sn(O t Am)4]]> 2 120 <![CDATA[MeSn(O t This)3]]> 0.1 ~57 <![CDATA[ n This is Sn(O t This)3]]> 0.9 100 <![CDATA[ n BuSn(NMe2)3]]> 0.05 80

[0093] In CVD processes, two or more reactant gases are typically mixed in a chamber near the substrate surface. Therefore, sufficient stability can be designed into the reaction conditions to control undesirable gas phase reactions and nucleation. ALD precursors introduced separately and sequentially into the reaction chamber typically react with chemically adsorbed co-precursors or decomposition products that permeate the substrate surface. n S X (4-n) Desirable characteristics of the precursor include, for example, sufficient volatility for gas phase delivery in the system, thermal stability to prevent premature decomposition, and suitable reactivity to react with the co-precursors to produce the target product under specified process conditions. The pressure and temperature in the reaction chamber can be selected to control the reaction process.

[0094] In general, the precursor with relatively low vapor pressure can be introduced into the gasification chamber using the flow, spraying and / or direct liquid injection of steam. A flash evaporator can be used to introduce the precursor vapor of a controlled amount into the reaction chamber to control the reaction process in the chamber accordingly. The second reactant driving hydrolysis / oxidation can be introduced into the chamber by a separate inlet. Commercial CVD devices may be suitable for this purpose or specific equipment may be used. To promote deposition, the substrate may be heated or cooled according to the precursor characteristics. Inert gases such as N2, Ar, etc. may be used as carrier gas, purification gas, or pressure regulating gas in a suitable capacity using a sequential and continuous flow scheme.

[0095] As shown, a series of Rn S X (4-n) Compounds (where n=0, 1 or 2) or combinations thereof, as discussed herein, produce organotin oxide hydroxide resists by hydrolysis in solution or in situ, which may also be suitable for vapor deposition of organotin oxide hydroxide resists having desired properties. Suitable X ligands include alkyl amides and dialkyl amides, chloro, alkyl oxo, or hydrocarbyl, siloxo, silyl amide, disilyl amide, aryl oxo, azido, amide, amido or fluorinated analogs thereof in combination with hydrocarbyl R groups, including straight and branched chain alkyl, cycloalkyl, aryl, alkenyl, alkynyl, benzyl and fluorinated derivatives thereof. Suitable precursors may include, for example, (CH3)3CSn(NMe2)3, (CH3)2CHSn(NMe2)3, (CH3)2(CH3CH2)CSn(NMe2)3, (CH2)2CHSn(NMe2)3, CH3Sn(NMe2)3, (CH2)3CHSn(NMe2)3, (CH2)4CHSn(NMe2)3, (C6H5)CH2Sn(NMe2)3, (C6H5)(CH3)CHSn(NMe2)3, (C6H5)(CH3)CHSn(NMe2)3, (C6H5)(CH3)CHSn(NMe2)3, (CH3)2(CN)CSn(NMe2)3, (CH3)(CN)CHSn(NMe2)3, or (CH3)3CSn(O t Bu)3、(CH3)2CHSn(O t Bu)3、(CH3)2(CH3CH2)CSn(O t Bu)3、(CH2)2CHSn(O t Bu)3, CH3Sn(O t Bu)3、(CH2)3CHSn(O t Bu)3、(CH2)4CHSn(O t Bu)3、(C6H5)CH2Sn(O t Bu)3、(C6H5)(CH3)CHSn(O t Bu)3、(C6H5)(CH3)CHSn(O t Bu)3、(CH3)2(CN)CSn(O t Bu)3、(CH3)(CN)CHSn(O t In addition, one or more vapor phase precursor compounds such as Sn(NMe2)4 or Sn(OtBu)4 with a concentration of 0.0 can be reacted with the organotin-containing precursor sequentially or simultaneously to modify the R:Sn ratio in the film to achieve the desired patterning properties.

[0096] Accordingly, the hydrolyzable compound can be directly deposited as the corresponding alkyltin oxide hydroxide coating by vapor phase hydrolysis, which can then be suitably patterned. Advantages of vapor deposition can include, for example, reduced resist film defect density, improved thickness and compositional uniformity, and conformal and sidewall coating of the substrate surface shape.

[0097] The vapor deposition method is used to directly deposit an organotin oxide hydroxide having the general formula RSnO (3 / 2-x / 2) (OH) x (0 < x < 3) and may in some embodiments include an inert gas source connected to a separate heated bubbler vessel. The first vessel contains a liquid alkyl tris(dialkylamido)tin compound having a sufficient vapor pressure to produce a suitable partial pressure for transport in an inert carrier gas. The second vessel contains liquid water or a water / alcohol mixture. By controlling the vessel temperature, inert gas flow rate, and total system pressure, the gaseous RSn(NR'2)3 and H2O are separately delivered to a chamber that is evacuated to <about 0.1 Torr, more generally about 0.01 Torr to about 25 Torr, and in some atmospheric pressure CVD pressures >25 Torr. The precursors herein are mixed and reacted to deposit an organotin oxide hydroxide on the substrate. The substrate and / or the chamber and / or the vapor can be heated to facilitate the reaction and deposition on the substrate surface. In some embodiments, a reaction temperature below about 200 °C is desired to limit the dealkylation of the tin compound and / or prevent excessive dehydration and condensation of the oxide hydroxide. The formation of these oxide hydroxides can reduce the photoresist dissolution rate contrast between the exposed and unexposed areas. In various embodiments, the gas, chamber walls, and / or substrate can typically be heated to a temperature of about 40 °C to about 175 °C, and in additional embodiments to a temperature of about 50 °C to about 160 °C. Those skilled in the art will recognize that additional ranges of pressure and temperature within the explicit ranges above are covered and within the scope of the present invention. In a similar related process, pulses of water vapor, inert gas, and RSn(NR'2)3 of suitable duration and frequency can be alternated to enable the limited surface adsorption and common reaction schemes of the ALD method.

[0098] Patterning and patterned structural properties

[0099] After hydrolysis, condensation and drying, radiation can be used to finely pattern the coating material. As mentioned above, the composition of the precursor solution and therefore the corresponding coating material can be designed to fully absorb the desired form of radiation. The absorption of radiation produces energy that can destroy the bond between the metal and the alkyl ligand, so that at least some alkyl ligands are no longer available to stabilize the material. Depending on the process variables and the identification of such products, the radiation decomposition products including alkyl ligands or fragments can diffuse out of the film or cannot diffuse out of the film. With the absorption of sufficient amounts of radiation, the exposed coating material condenses, i.e., forms an enhanced metal oxo-hydroxyl network structure, which may include additional water absorbed from the ambient atmospheric pressure. Radiation can usually be delivered according to a selected pattern. The radiation pattern is converted into a corresponding pattern or latent image in a coating material having an irradiated area and an unirradiated area. The irradiated area contains a chemically modified coating material, and the unirradiated area usually contains a formed coating material. As mentioned below, an extremely smooth edge can be formed when developing the coating material, while removing the unirradiated coating material, or optionally selectively removing the irradiated coating material.

[0100] The radiation may be directed to the coated substrate, typically by a mask, or the radiation beam may be controllably scanned across the substrate. In general, the radiation may comprise electromagnetic radiation, an electron beam (beta radiation), or other suitable radiation. In general, the electromagnetic radiation may have a desired wavelength or range of wavelengths, such as visible radiation, ultraviolet radiation, or x-ray radiation. For radiation patterns, the useful resolution generally depends on the wavelength of the radiation, and higher resolution patterns may generally be achieved with shorter wavelength radiation. Thus, it may be desirable to use ultraviolet light, x-ray radiation, or an electron beam to achieve particularly high resolution patterns.

[0101] Ultraviolet light extends between wavelengths greater than or equal to 100 nm and less than 400 nm, following the international standard ISO 21348 (2007), which is incorporated herein by reference. A krypton fluoride laser can be used as a light source for 248 nm ultraviolet light. The ultraviolet range can be subdivided in several ways under recognized standards, such as extreme ultraviolet (EUV) (greater than or equal to 10 nm to less than 121 nm) and far ultraviolet (FUV) (greater than or equal to 122 nm to less than 200 nm). The 193 nm line from an argon fluoride laser can be used as a radiation source in FUV. EUV light has been used for lithography at 13.5 nm, and this light is produced from a Xe or Sn plasma source excited using a high energy laser or discharge pulse. Soft x-rays can be defined from greater than or equal to 0.1 nm to less than 10 nm.

[0102] The amount of electromagnetic radiation can be characterized by a flux or dose, which is defined by the integrated radiation flux over the exposure time. A suitable radiation flux may be about 1 mJ / cm 2 About 150mJ / cm 2, in another embodiment, about 2 mJ / cm 2 About 100mJ / cm 2 , and in further embodiments is about 3 mJ / cm 2 to about 50mJ / cm 2 Those skilled in the art will recognize that additional ranges of radiant flux within the explicit ranges above are contemplated and within the present invention.

[0103] With electron beam lithography, the electron beam typically induces secondary electrons, which typically modify the irradiated material. Resolution may vary at least in part with the range of the secondary electrons in the material, with higher resolutions generally believed to result from shorter range secondary electrons. Based on the high resolution achievable with electron beam lithography using the inorganic coating materials described herein, the range of secondary electrons in the inorganic material is limited. The electron beam may be characterized by the energy of the beam, and suitable energies may be in the range of about 5V to about 200kV (kilovolts), and in other embodiments, in the range of about 7.5V to about 100kV. The proximity corrected beam dose at 30kV may be in the range of about 0.1 microcoulombs / cm2 to about 5 microcoulombs / cm2 (mC / cm 2 ), in another embodiment, about 0.5 μC / cm 2 to about 1mC / cm 2 , and in other embodiments is about 1 μC / cm 2 to about 100μC / cm 2 Those skilled in the art can calculate corresponding doses at other beam energies based on the teachings herein and will recognize that additional ranges of electron beam characteristics within the above explicit ranges are encompassed and within the present invention.

[0104] Based on the design of the coating material, there may be a greater contrast in material properties between the irradiated area with condensed coating material and the non-irradiated coating material with substantially intact organic ligands. It has been found that the contrast at a given dose can be improved with a post-irradiation heating treatment, although satisfactory results can be achieved without a post-irradiation heating treatment in some embodiments. The post-exposure heat treatment appears to anneal the irradiated coating material to increase its condensation without significantly condensing the non-irradiated area of ​​the coating material based on the thermal destruction of the organic ligand-metal bond. For embodiments using post-irradiation heat treatment, the post-irradiation heat treatment may be performed at a temperature of about 45°C to about 250°C, about 50°C to about 190°C in additional embodiments, and about 60°C to about 175°C in additional embodiments. Post-exposure heating may typically be performed for at least about 0.1 minutes, about 0.5 minutes to about 30 minutes in additional embodiments, and about 0.75 minutes to about 10 minutes in additional embodiments. Those skilled in the art will recognize that additional ranges of post-irradiation heating temperatures and times within the above explicit ranges are encompassed and within the present invention. This high contrast in material properties further facilitates the formation of high resolution lines with smooth edges in the pattern after development as described in the following section.

[0105] After exposure to radiation, the coating material is patterned with irradiated areas and non-irradiated areas. Figure 1 and Figure 2 , a patterned structure 100 is shown including a substrate 102, a thin film 103, and a patterned coating material 104. The patterned coating material 104 includes regions 110, 112, 114, 116 of irradiated coating material and uncondensed regions 118, 120, 122 of unirradiated coating material. The pattern formed by the condensed regions 110, 112, 114, 116 and the uncondensed regions 118, 120, 122 presents a latent image in the coating material, and the development of the latent image is discussed in the following section.

[0106] Developing and patterning structures

[0107] Development of the image involves contacting the patterned coating material including the latent image with a developer composition to remove the non-radiated coating material to form a negative image or to remove the radiated coating to form a positive image. Using the resist materials described herein, effective negative patterning or positive patterning with a desired resolution can generally be performed using a suitable developing solution and generally based on the same coating. Specifically, the radiated area is at least partially condensed to increase the metal oxide characteristics so that the radiated material is resistant to dissolution by organic solvents, while the non-radiated composition remains soluble in organic solvents. Reference to the condensed coating material refers to at least partial condensation in the sense of increasing the oxide characteristics of the material relative to the original material. On the other hand, due to the hydrophobicity of the material, the non-radiated material is less soluble in weak alkaline aqueous solutions or weak acid aqueous solutions, so alkaline aqueous solutions can be used to remove the radiated material while maintaining the positive patterning of the non-radiated material.

[0108] Coating compositions with organic stabilizing ligands produce inherently hydrophobic materials. Irradiation to break at least some of the organometallic bonds converts the material to a less hydrophobic, i.e., more hydrophilic, material. These changes in characteristics provide a distinct contrast between irradiated and non-irradiated coatings, which provides the ability to perform both positive and negative patterning on the same resist composition. Specifically, the irradiated coating material is condensed to a more metal oxide composition to some extent; however, the degree of condensation is generally moderate without significant heating, so that the irradiated material can be developed relatively simply using a suitable developer.

[0109] See also Figure 3 and Figure 4 , relative to negative tone imaging, has been developed by contact with a developer to show Figure 1 and Figure 2 The latent image of the structure in the substrate 102 is formed to form a patterned structure 130. After the image is developed, the substrate 102 is exposed along the top surface through openings 132, 134, 135. The openings 132, 134, 135 are located at the locations of the uncondensed areas 118, 120, 122, respectively. Figure 5 and Figure 6 , relative to positive tone imaging, the developed Figure 1 and Figure 2 The latent image of the structure in the patterned structure 130 is formed to form a patterned structure 140. The patterned structure 140 has a conjugate image of the patterned structure 130. The patterned structure 140 has the substrate 102 at locations exposed to the radiation regions 110, 112, 114, 116, which are developed to form openings 142, 144, 146, 148.

[0110] For negative imaging, the developer may be an organic solvent, such as a solvent used to form a precursor solution. In general, developer selection may be affected by solubility parameters associated with the coating material, irradiation and non-irradiation, as well as developer volatility, flammability, toxicity, viscosity, and possible chemical interactions with other processing materials. Specifically, suitable developers include, for example, aromatic compounds (e.g., benzene, xylene, toluene), esters (e.g., propylene glycol monomethyl acetate, ethyl acetate, ethyl lactate, n-butyl acetate, butyrolactone), alcohols (e.g., 4-methyl-2-pentanol, 1-butanol, isopropanol, 1-propanol, methanol), ketones (e.g., methyl ethyl ketone, acetone, cyclohexanone, 2-heptanone, 2-octanone), ethers (e.g., tetrahydrofuran, dioxane, anisole), etc. Development may be performed for about 5 seconds to about 30 minutes, in other embodiments for about 8 seconds to about 15 minutes, and in additional embodiments for about 10 seconds to about 10 minutes. Those skilled in the art will recognize that additional ranges within the explicit ranges above are encompassed and are within the present invention.

[0111] For positive imaging, the developer can generally be an acidic aqueous solution or an alkaline aqueous solution. In some embodiments, an aqueous base can be used to obtain a clearer image. To reduce contamination from the developer, it may be desirable to use a developer that does not have metal atoms. Therefore, a quaternary ammonium hydroxide composition (such as tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide or a combination thereof) is satisfactory as a developer. In general, the quaternary ammonium hydroxides that have received much attention can be represented by the formula R4NOH, where R=methyl, ethyl, propyl, butyl or a combination thereof. The coating materials described herein, especially tetramethylammonium hydroxide (TMAH), can generally be developed with the same developer currently used for polymer resists. Commercial TMAH can be obtained at 2.38 weight percent, and this concentration can be used for the treatment described herein. In addition, mixed tetraalkyl quaternary ammonium hydroxides can be used. Generally speaking, the developer may include from about 0.5 weight percent to about 30 weight percent, in further embodiments from about 1 weight percent to about 25 weight percent, and in other embodiments from about 1.25 weight percent to about 20 weight percent of a tetraalkylammonium hydroxide or similar quaternary ammonium hydroxide. Those skilled in the art will recognize that additional ranges of developer concentrations within the explicit ranges above are contemplated and within the present invention.

[0112] In addition to the basic developer composition, the developer may contain additional compositions to facilitate the development process. Suitable additives include, for example, dissolved salts with cations selected from the group consisting of ammonium, d-block metal cations (hafnium, zirconium, lanthanum, etc.), f-block metal cations (cerium, lutetium, etc.), p-block metal cations (aluminum, tin, etc.), alkali metals (lithium, sodium, potassium, etc.) and combinations thereof; and dissolved salts with anions selected from the group consisting of fluoride, chloride, bromide, iodide, nitrate, sulfate, phosphate, silicate, borate, peroxide, butanol, formates, oxalates, ethylenediaminetetraacetic acid (EDTA), tungstates, molybdates, etc. and combinations thereof. Other potentially applicable additives include, for example, molecular chelating agents such as polyamines, alcohol amines, amino acids, carboxylic acids, or combinations thereof. If there are additives selected as appropriate, the developer may contain no more than about 10 weight percent of additives, and in another embodiment no more than about 5 weight percent of additives. One skilled in the art will recognize that additional ranges of additive concentrations within the explicit ranges above are contemplated and within the present invention. Additives may be selected to improve contrast, sensitivity, and line width roughness. Additives in the developer may also inhibit the formation and deposition of metal oxide particles.

[0113] For weaker developers (e.g., lower concentrations of aqueous developers, diluted organic developers, or compositions in which the coating has a lower development rate), a higher temperature development process can be used to increase the rate of the process. For stronger developers, the temperature of the development process can be lower to reduce the rate and / or control the kinetics of development. In general, the temperature of the development can be adjusted between suitable values ​​consistent with the volatility of the solvent. In addition, ultrasound can be used during development to disperse the developer with dissolved coating material near the developer coating interface.

[0114] The developer can be applied to the patterned coating material using any reasonable method. For example, the developer can be sprayed onto the patterned coating material. In addition, spin coating can be used. For automated processing, a liquid coating method can be used, which involves pouring the developer onto the coating material in a fixed form. If necessary, spin rinsing and / or drying can be used to complete the development process. Suitable rinsing solutions include, for example, ultrapure water, methanol, ethanol, propanol and combinations thereof for negative patterning, and ultrapure water for positive patterning. After developing the image, the coating material is placed on the substrate as a pattern.

[0115] After the development step is completed, the coating material may be heat treated to further condense the material and to further dehydrate, densify or remove residual developer from the material. For embodiments in which the oxide coating material is incorporated into the final device, the heat treatment may be desirable, although for some embodiments in which the coating material is used as a resist, heat treatment may be required and ultimately removed if it is desirable to promote the stability of the further patterned coating material. Specifically, the baking of the patterned coating material may be performed under conditions in which the patterned coating material exhibits a desired level of etching selectivity. In some embodiments, the patterned coating material may be heated to a temperature of about 100°C to about 600°C, about 175°C to about 500°C in other embodiments, and about 200°C to about 400°C in additional embodiments. The heating may be performed for at least about 1 minute, about 2 minutes to about 1 hour in other specific embodiments, and about 2.5 minutes to about 25 minutes in other embodiments. The heating may be performed in air, vacuum, or an inert gas environment (such as Ar or N2). Those skilled in the art will recognize that additional ranges of temperature and time for thermal treatment within the above explicit ranges are encompassed and within the present invention. Likewise, non-thermal treatments including blanket UV exposure or exposure to an oxidizing plasma such as O2 may also be employed for similar purposes.

[0116] For conventional organic resists, if the aspect ratio (height divided by width) of the structure becomes too large, the structure is susceptible to pattern collapse. Pattern collapse can be associated with mechanical instability of higher aspect ratio structures so that forces associated with processing steps (e.g., surface tension) distort structural components. Lower aspect ratio structures are more stable relative to potential distortion forces. For the patternable coating materials described herein, due to their higher etch resistance and ability to effectively process structures with thinner layers of coating materials, improved patterning can be accomplished without the need for patterned coating materials with higher aspect ratios. Therefore, extremely high resolution features have been formed without the aid of higher aspect ratio shapes in patterned coating materials.

[0117] The resulting structure may have sharp edges with very low line width roughness. Specifically, in addition to the ability to reduce line width roughness, high contrast also allows the formation of small features and spaces between features, as well as the ability to form very well resolved two-dimensional patterns (e.g., sharp corners). Therefore, in some embodiments, adjacent linear segments of adjacent structures may have an average spacing (half-pitch) of no more than about 60nm (30nm half-pitch), in some embodiments no more than about 50nm (25nm half-pitch), and in other embodiments no more than about 34nm (17nm half-pitch). The spacing can be evaluated by design and confirmed using scanning electron microscopy (SEM) (such as using top-down imaging). As used herein, spacing refers to the spatial spacing, or the center-to-center distance of a repeating structural component, and as commonly used in the art, half-pitch is half of the spacing. The characteristic size of the pattern can also be described relative to the average width of the feature, and the size is usually evaluated away from corners, etc. In addition, a feature can refer to the gap between material components and / or material components. In some embodiments, the average width may be no more than about 25 nm, in other embodiments no more than about 20 nm, and in additional embodiments no more than about 15 nm. The average line width roughness may be no more than about 5 nm, in some embodiments no more than about 4.5 nm, and in other embodiments about 2.5 nm to about 4 nm. The line width roughness is evaluated by analysis of top-down SEM images to derive a 3σ deviation from the average line width. The average value contains high-frequency and low-frequency roughness, i.e., short correlation lengths and long correlation lengths, respectively. The line width roughness of organic resists is mainly characterized by long correlation lengths, while the organic metal coating materials of the present invention exhibit significantly shorter correlation lengths. In the pattern transfer process, short correlation roughness may be smoothed during the etching process, thereby producing a pattern with higher fidelity. Those skilled in the art will recognize that spacing, average width, and line width roughness within the above-defined ranges are encompassed and within the present invention. Based on these processes, patterning can be debugged to form various devices such as electronic integrated circuits, typically by repeated patterning processes to form appropriately layered structures such as transistors or other components.

[0118] Wafer throughput is essentially the limiting factor for EUV lithography implemented in high-volume semiconductor manufacturing and is directly related to the dose required to pattern a given feature. However, despite the existence of chemical strategies to reduce the amount of imager, in EUV photoresists with feature sizes and spacings <50nm, a negative correlation between the amount of imager required to print the target features and the feature size uniformity (such as LWR) is generally observed, limiting the operability of the final device and wafer yield. However, it has been found that the precursors, precursor solutions, and photoresist films described herein avoid this limitation and are able to reduce the EUV imager dose within a rough dose range without increasing LWR. When processed under similar conditions, by utilizing R comprising in-situ hydrolysis during the coating and baking steps as detailed in the following examples, n S X (4-n) For precursor solutions of blends of SnX4 and SnX4, >30% dose reduction at equal or lower LWR was observed relative to photoresist films derived from a mixture of prehydrolyzed organotin oxide hydroxide compounds (prepared according to the method described in the '839 application).

[0119] Based on the improved process described in the following examples, the improved properties of the coating material can be characterized accordingly. For example, a substrate comprising an inorganic semiconductor layer and a radiation-sensitive coating material along the surface can be patterned with EUV light having a wavelength of 13.5 nm in a pattern of 16 nm lines on a 32 nm pitch. To evaluate the coating material, the dose used to obtain a critical dimension of 16 nm can be evaluated along with the achievable line width roughness (LWR). The improved coating can be treated with about 8 mJ / cm 2 to about 25mJ / cm 2 The critical dimension (CD) and line width roughness (LWR) of the resist were extracted from the SEM images using SuMMIT analysis software (EUV Technologies, Inc.).

[0120] In other embodiments, the improved patterning capability can be expressed in terms of gelling agent values. A structure comprising a substrate and a radiation-sensitive coating comprising an alkyl metal oxide hydroxide can have a radiation intensity of no more than about 6.125 mJ / cm2, and in other embodiments about 5.5 mJ / cm 2 to about 6mJ / cm 2 The evaluation of the gelling amount is explained in the following examples.

[0121] References (incorporated herein by reference):

[0122] 1) Maeng, WJ; Pak, SJ; Kim. HJVac.Sci.Tech B. 2006, 24, 2276.

[0123] 2) Rodríguez-Reyes, JCF; Teplyakov, AVJ Appl. Phys. 2008, 104, 084907.

[0124] 3) M.; Ritala, M. Thin Solid Films 2002, 409, 138.

[0125] 4) M.; Ritala, MJPhys.IV 1999, 9, Pr8-852.

[0126] 5) Atagi, LM; Hoffman, DM; Liu, JR; Zheng, Z.; Chu, WK; Rubiano, RR; Springer, RW;

[0127] Example

[0128] Example 1 - Preparation of Precursors for In-Situ Hydrolysis

[0129] This example involves the formation of an organotin amide-based compound suitable for in situ hydrolysis to form an organotin oxide hydroxide coating.

[0130] Follow the report on The precursor tert-butyl tris(diacetamido)tin (tBuSn(NEt2)3, hereinafter P-1) was synthesized by the method of D.; Puff, H.; Beckerman, NJ Organomet. Chem. 1985, 293, 191 (which is incorporated herein by reference). Tetrakis(diacetamido)tin and tBuLi reagents were purchased from Sigma-Aldrich and used without further purification. The reagents were reacted in stoichiometric quantities in anhydrous hexane (Sigma-Aldrich) at -78°C. The deposited lithium amide salts were removed by filtration and the product was rinsed with hexane, and the solvent was removed under vacuum. The crude product was distilled under vacuum (about 0.3 torr at 95°C).

[0131] Weigh 1.177 g (3.0 mmol) of P-1 in a 30 mL amber glass bottle. Prepare the solution in a glove box filled with Ar, then add 15 mL of anhydrous 4-methyl-2-pentanol (dried over 3A molecular sieves for 24 h). Cap and agitate the bottle. Dilute 1 part of the stock solution in 2.85 parts (volume) of anhydrous 4-methyl-2-pentanol before coating.

[0132] The precursor isopropyl tris(dimethylamino)tin (iPrSn(NMe2)3, hereinafter P-2) was synthesized under an inert atmosphere and then dissolved in toluene to form a resist precursor solution. Under argon, a 1L Schlenk-adapted round-bottom flask was charged with LiNMe2 (81.75 g, 1.6 mol, Sigma-Aldrich) and anhydrous hexane (700 mL, Sigma-Aldrich) to form a slurry. A larger stirring bar was added and the container was sealed. The addition funnel under positive argon pressure was flushed with iPrSnCl3 (134.3 g, 0.5 mol, Gelest) and then connected to the reaction flask. The reaction flask was cooled to -78°C, and then iPrSnCl3 was added dropwise over a period of 2 hours. The reaction was allowed to warm to room temperature while stirring overnight. The reaction produced a byproduct solid. After standing, the solid was filtered through an inline cannula filter under positive argon pressure. The solvent was then removed under vacuum, and the residue was distilled under reduced pressure (50° C. to 52° C., 1.4 mmHg) to give a pale yellow liquid (110 g, 75% yield). The distillate in C6D6 solvent was collected on a Bruker DPX-400 (400 MHz, BBO probe) spectrometer. 1 H and 119 Sn NMR spectrum. Observed 1 The H resonances (s, 2.82 ppm, -N(CH3)2; d, 1.26 ppm, -CH3; m, 1.60 ppm, -CH) match the spectrum predicted for iPrSn(NMe2)3. The fundamental 119 The Sn resonances are consistent with a major product having a monotin environment; the chemical shifts are similar to those reported for monoalkyltris(dialkylamido)tin compounds.

[0133] Weigh 0.662 g (2.25 mmol) of P-2 in a 30 mL amber glass bottle to prepare a solution in a glove box filled with Ar. Then add 15 mL volume of anhydrous toluene (dried on 3A molecular sieves for 24 h) to make a stock solution (SOL-2). Then cap and agitate the bottle. Dilute 1 part of the stock solution in 3 parts (volume) of anhydrous toluene before coating.

[0134] Example 2 - Patterning of in-situ hydrolyzed photoresist coatings

[0135] This example shows successful in-situ hydrolysis of a coating formed from the composition of Example 1 and subsequent EUV patterning.

[0136] The films were deposited on silicon wafers (100 mm diameter) with a native oxide surface. The Si wafers were treated with hexamethyldisilazane (HMDS) vapor primer prior to deposition of the amide precursor. A solution of P-1 in 4-methyl-2-pentanol was spin-coated on the substrate at 1500 rpm in air and baked on a hot plate at 100 °C in air for 2 min to evaporate residual solvent and volatile hydrolysis products. The film thickness after coating and baking should be about 31 nm as measured by ellipsometry.

[0137] The coated substrate was exposed to extreme ultraviolet radiation (Lawrence Berkeley National Laboratory Micro Exposure Tool). A pattern of 17nm lines on 34nm spacing was projected onto the wafer using 13.5nm wavelength radiation, dipole illumination, and a numerical aperture of 0.3. The patterned resist and substrate were then subjected to post-exposure baking (PEB) on a hot plate at 170°C in air for 2min. The exposed film was then immersed in 2-heptanone for 15 seconds, followed by rinsing with the same developer for another 15 seconds to form a negative image, i.e., to remove the unexposed portions of the coating. After development, a final 5min hot plate bake was performed at 150°C in air. Figure 7 The SEM image of a 16.7 nm resist line is shown, which is generated by 56 mJ / cm 2 EUV dose and calculated P-1 cast on 4-methyl-2-pentanol at 34nm pitch at 2.6nm LWR.

[0138] A second film was cast from a toluene solution of P-2 using coating and baking conditions consistent with those described above. A linear array of 50 circular plates with a diameter of approximately 500 μm was projected onto the wafer using EUV light. The plate exposure time was adjusted to increase the EUV dose delivered for each plate from 1.38 mJ cm to 1.5 mJ cm with a gradient index of 7%. -2 Increased to 37.99 mJ cm -2 After the PEB, development and final bake processes described above, a JA Woollam M-2000 spectroscopic ellipsometer was used to measure the residual thickness of the exposed panels. Figure 8 In Figure 1, the thickness of each plate is plotted as a function of the delivered EUV dose. The resulting curve clearly shows the negative contrast generated upon exposure, with the residual film thickness starting at about 0 and ending at approximately 15.8 mJ cm -2 The maximum value (gelling amount, Dg) is reached at the delivered dose.

[0139] Example 3 - Evaluation of In-Situ Hydrolyzed Coatings

[0140] This example provides evidence of substantially complete hydrolysis by the in situ hydrolysis method for precursors with hydrolyzable Sn bonds.

[0141] For comparison, isopropyltin oxide hydroxide was prepared for forming a radiation-sensitive coating. The solid hydrolysis product of isopropyltin trichloride (iPrSnCl3, Gelest) was prepared by rapidly adding 6.5 g (24 mmol) of isopropyltin trichloride to 150 mL of 0.5 M NaOH (aq.) and stirring vigorously, thereby immediately producing a precipitate. The resulting mixture was stirred at room temperature for 1 h and then filtered using No. 1 filter paper (Whatman). The retained solid was washed three times with ~25 mL portions of DI H2O and then dried under vacuum (about 5 Torr) at room temperature for 12 h. Elemental analysis of the dried powder (18.04% C, 3.76% H, 1.38% Cl; Microanalysis, Inc.; Wilmington, DE) indicated that the chloride ions and i PrSnO (3 / 2-(x / 2)) (OH) x (where x≈1) is the approximate empirical formula of the hydrolysis product (hereinafter P-3). (The calculated values ​​of C3H8O2Sn are: 18.50% C, 4.14% H, 0.00% Cl).

[0142] The solid-state hydrolyzate iPrSnO was prepared by dissolving the dried powder in 2-butanone to a total Sn concentration of approximately 0.25 M. (3 / 2-(x / 2)) (OH) x of solutions. A solution of P-2 in anhydrous 4-methyl-2-pentanol was prepared by adding 1.47 g (5.0 mmol) of P-2 to 10 mL of 4-methyl-2-pentanol as previously described. Thin films were cast by spin coating each solution onto a 25 mm x 25 mm Si wafer. The solution of P-2 was coated at 2000 rpm while the solution of P-3 was coated at 1250 rpm. After coating, each film was baked at 150°C in air for 2 minutes. Alcohols can react with P-2 to form alkoxide ligands, but in any case, if alkoxide ligands are formed, these ligands appear to be further hydrolyzed to form oxide hydroxide compositions.

[0143] Fourier transform infrared (FTIR) transmission spectra of the two films were collected on a Nicolet 6700 spectrometer using a bare substrate from the background art. Figure 8 ) are very similar in nature, indicating substantial hydrolysis and elimination of the amide / alkyloxy groups from the P-2 solution and deposition of the oxide hydroxide in both cases. Specifically, 2800-3000 cm-1 and 1100-1500cm -1 The regions of the two films are almost identical, indicating that the similar CH x composition, and no substantial CN substance is present.

[0144] Example 4 - Preparation of a hydrolyzable precursor having a tetra-dialkylamide or tert-butoxytin compound

[0145] This example describes the formation of mixed hydrolyzable precursor compounds to provide control of the stoichiometry of the radiation-sensitive ligand relative to the metal in the radiation-sensitive coating.

[0146] Tert-butyl tris(diacetamido)tin was synthesized as described in Example 1. Tetrakis(dimethylamido)tin (Sn(NMe2)4, FW=295.01) was purchased from Sigma-Aldrich and used without further purification.

[0147] Tin (IV) tert-butoxide (Sn(O t Bu)4, FW = 411.16, hereinafter P-5): Stannous chloride (152g / 0.8mol) and pentane (1L) are added to a 3L oven-dried round-bottom flask equipped with a magnetic stirring bar and purged with nitrogen. A 1L balanced pressure addition funnel equipped with a nitrogen pressure inlet is charged with diethylamine (402mL / 3.9mol) and pentane (600mL), which is then connected to the flask and immersed in an ice bath. The amine solution is then added dropwise to maintain a slow reflux. After the addition of the amines is complete, pentane (50mL) containing 2-methyl-2-propanol (290g / 3.9mol) is added to the addition funnel and then dropwise to the flask. After stirring for 18 hours, the slurry is transferred to an air-free sintered filter bottle and precipitated to remove salts. The solvent is removed under reduced pressure and the target compound (BP = 60-62C @ 1 Torr) is distilled. 1 H NMR (C6D6): 1.45 ppm (s); 119 Sn NMR(C6D6): -371.4ppm(s).

[0148] P-1 ( t BuSn(NEt2)3, hereinafter S-1), P-4(Sn(NMe2)4, hereinafter S-2) and P-5(Sn(O tAdditional dry 4-methyl-2-pentanol was then added to dilute the solution to a final concentration of 0.25 M (Sn).

[0149] Another stock solution, S-4, was prepared by inserting 41 g of P-1 into a round-bottom flask submerged in an isopropanol / dry ice bath and containing 250 mL of methanol while stirring on a magnetic stir plate. t After BuSn(NEt2)3 aliquots, remove the flask containing the mixture from the ice bath and allow it to reach room temperature. Then, the flask equipped with the mixture is heated to 50°C in a water bath connected to a rotary evaporator, and the solvent is removed under reduced pressure (10 mTorr) until the solvent is substantially evaporated and a viscous yellow oil is obtained. Finally, the yellow oil is dissolved in 1.0 L of 4-methyl-2-pentanol. After solvent evaporation and subsequent thermal decomposition of residual SnO2 solids, the resulting solution has a molar concentration of 0.097 M [Sn] based on the residual mass determination of the solution.

[0150] Precursor coating solutions CS-a, CS-b, and CS-c were prepared by mixing the S-1 stock solution with the S-2 stock solution at volume ratios of 0, 5:1, and 9:1 to produce coating solutions, wherein the total Sn concentrations in the mixture were derived from Sn(NMe2)4 at 0(a), 10(b), and 20(c) mol%. Prior to spin coating, these solutions were then further diluted to 0.070 M (total Sn) with 4-methyl-2-pentanol. For example, to prepare 200 mL of CS-b, 5.6 mL of the stock solution prepared from Sn(NMe2)4 (S-2) was added to the 200 mL of CS-c prepared from Sn(NMe2)4 (S-2). t 50.4 mL of a solution of BuSn(NEt2)3(S-1) was prepared, mixed vigorously, and diluted to 200 mL total volume with dry 4-methyl-2-pentanol. A summary of the precursor coating solutions, concentrations, and compositions are shown in Table 2.

[0151] Stock solution S-4 was mixed with stock solutions S-2 and S-3 in appropriate volume ratios so that 10 mol % and 20 mol % of the total Sn concentration came from Sn(NMe2)4 (CS-e and CS-f, respectively) and Sn(O t Bu)4 (CS-g, CS-h) and diluted with dry 4-methyl-2-pentanol to prepare a precursor coating solution CS-eh with a total Sn concentration of 0.044M. The stock solution S-4 was directly diluted with dry 4-methyl-2-pentanol to a final concentration of 0.042M Sn to prepare the precursor coating solution CS-d. As an example, 72.6mL of S-4 was mixed with 7.04mL of S-3 and diluted with dry 4-methyl-2-pentanol to a total volume of 200mL to prepare 200mL of the precursor coating solution CS-e.

[0152] Table 2

[0153]

[0154] Precursor coating solution CS-i was prepared by mixing a methanol solution containing the prehydrolyzed tert-butyltin oxide hydroxide hydrolyzate with a 4-methyl-2-pentanol solution of the prehydrolyzed isopropyltin oxide hydroxide hydrolyzate and diluting the resulting mixture to 0.03 M [Sn] with a pure solvent as described in the '839 application. The resulting solution was characterized as i PrSnO (3 / 2-(x / 2)) (OH) x and t BnS (3 / 2-(x / 2)) (OH) x A blend of hydrolyzate, wherein relative to the total molar amount of Sn, t-BuSnO (3 / 2-(x / 2)) (OH) x The score is 40%.

[0155] Example 5 - Patterning of engineered coatings with selected levels of radiation-sensitive ligands

[0156] This example presents results obtained by patterning a coating formed with a coating solution prepared as described in Example 4 which demonstrates improved patterning with a lower radiation dose.

[0157] By t BuSn(NEt2)3 and some coating solutions Sn(NMe2)4 or Sn(O t The tert-butyltin oxide hydroxide photoresist film was deposited by using the precursor coating solution of Example 4 prepared with Bu)4 and then exposed to EUV radiation. The film for EUV contrast curve was deposited on a silicon wafer (100 mm diameter) with a native oxide surface. The Si wafer was treated with hexamethyldisilazane (HMDS) vapor primer before deposition. The film was prepared by mixing the precursor coating solution of Example 4 with Bu)4 and then exposed to EUV radiation. The film was deposited on a silicon wafer (100 mm diameter) with a native oxide surface for EUV contrast curve ... t Precursor coating solutions CS-a, CS-b and CS-c (0.070M Sn) were prepared from BuSn(NEt2)3 and 0, 10 and 20 mol% Sn(NMe2)4 were spin coated on Si substrates at 1500 rpm in air and baked on a hot plate at 100°C in air for 2 min to remove residual solvent and volatile hydrolysis products. The film thickness measured by ellipsometry after coating and baking should be about 25-28 nm.

[0158] A linear array of 50 circular plates with a diameter of approximately 500 μm was exposed to EUV light on each wafer using a Lawrence Berkeley National Laboratory micro-exposure tool. The plate exposure time was adjusted to reduce the EUV dose delivered to each plate from 1.38 mJ cm to 2.5 mJ cm by a gradient index of 7%. -2 Increased to 37.99 mJ cm -2 . After exposure, the wafers were subjected to a post-exposure bake (PEB) on a hot plate in air at 170°C for 2 min. The exposed film was then immersed in 2-heptanone for 15 seconds and rinsed with the same developer for an additional 15 seconds to form a negative image, i.e., to remove the unexposed portions of the coating. After development, a final hot plate bake was performed at 150°C in air for 5 min. The residual thickness of the exposed panels was measured using an AJ.A.Woollam M-2000 pectroscopic ellipsometer. The measured thicknesses were normalized to the maximum resist thickness measured and plotted against the logarithm of the exposure dose to form a characteristic curve for each resist over a range of post-exposure bake temperatures. See Fig.10 The maximum slope of the normalized thickness versus (vs) logarithmic dose curve is defined as the resist contrast (γ), and the dose value at which the tangent is drawn through a point equal to 1 is defined as the resist gel dose (Dg). In this way, common parameters for resist characterization can be estimated following Mack, C. Fundamental Principles of Optical Lithography, John Wiley & Sons, Chichester, UK; pp 271-272, 2007.

[0159] The resulting curves clearly illustrate the negative contrast generated upon exposure, as the residual plate thickness of each resist film starts at about 0 and reaches a maximum value close to Dg. The reduction in the dose required to induce a change in the development rate is clearly observed as the mole fraction of Sn in the precursor coating solution corresponding to Sn(NMe2)4 increases from 0 (Dg) to 1. g =13.8mJ cm -2 ) increased to 10% (D g =10.6mJ cm -2 ) and finally 20% (D g =5.8mJ cm -2 ).

[0160] In the same manner, high-resolution line-space patterns were printed using an EUV scanner and tert-butyltin oxide hydroxide photoresist films were cast from the precursor coating solutions CS-d, CS-e, and CS-f. Silicon wafers (300 mm diameter) with a native oxide surface were used as substrates without additional surface treatment. The precursor coating solution CS-dh was prepared from tBuSn(NEt2)3, and 0, 10%, or 20 mol% of Sn(NMe2)4 or Sn(O2)4 as described above was added at 1000 rpm or 1500 rpm in air. t Bu) 4, and CS-i was spin-coated on a Si substrate (CS-d only) and baked on a hot plate at 100 °C for 2 min in air.

[0161] The coated substrates were exposed to extreme ultraviolet radiation using a NXE:3300B EUV scanner with dipole 60× illumination and a numerical aperture of 0.33. After a 2-minute 100°C post-coating bake (PAB), a pattern of 16nm lines on a 32nm pitch was projected onto the coated wafer. The exposed resist film and substrate were then subjected to PEB on a hot plate at 170°C in air for 2min. The exposed film was then developed in 2-heptanone for 15 seconds, followed by an additional 15-second rinse with the same developer to form a negative image, i.e., to remove the unexposed portion of the coating. After development, a final 5min hot plate bake was performed at 150°C in air. Fig.11 An SEM image of the resulting resist lines developed from a tert-butyltin oxide hydroxide photoresist film is shown. t BuSn(NEt2)3 (CS-d) and 10 mol% or 20 mol% Sn(NMe2)4 (CS-e, CS-f, respectively) or Sn(O t Figure 5 shows the shadow dose, critical dimension and line width roughness of each film cast from the precursor coating solution prepared from SnX4 (CS-g, CS-h). Similarly, with increasing fraction of SnX4 added to the precursor coating solution, a decrease in the shadow dose was observed. The shadow dose required to achieve a critical dimension of 16 nm was plotted relative to the calculated LWR. The films cast from the precursor coating solution di were plotted at Fig.12 Notably, a >30% reduction in the required imaging dose was obtained for films cast from CS-e and CS-f relative to CS-i without an accompanying increase in line width roughness (LWR), demonstrating substantial improvement over the pre-hydrolyzed mixed alkyl ligand formulation and an important circumvention (outside this dose range) of the typically observed inverse relationship between patterning dose and LWR.

[0162] Example 6-

[0163] The patterning performance was evaluated for coatings prepared with a mixture of tert-butyl and methyl radiation-sensitive ligands.

[0164] Specifically, in the case of comprising t Preparation of precursor solutions of BuSnX3 and MeSnX3 compounds t BnS (3 / 2-(x / 2)) (OH) x and MeSnO (3 / 2-(x / 2)) (OH) x In the case of organotin oxide hydroxide photoresist films of a mixture of the abovementioned materials, the precursor solution preparation, film coating and lithography performance were examined.

[0165] MeSn(O) was synthesized from MeSnCl3(Gelest) as follows t Bu)3 (FW = 353.1, P-6 below), a drying RBF equipped with an addition funnel and a magnetic stirring bar was charged with 0.8M of MeSnCl3 in pentane. While cooling with an ice bath, 4 molar equivalents of diethylamine in pentane (5.5M) were added dropwise through the addition funnel. After the addition was complete, 4 molar equivalents of tert-butyl alcohol mixed in pentane at 3.25:1 (vol) were added, and the solution was stirred at room temperature for 30 min. The reaction mixture was then filtered and the volatiles were removed under vacuum, leaving the product as a light oil. The product was then distilled at 55°C to 60°C at about 0.1 torr.

[0166] A stock solution of P-6 was prepared by dissolving in anhydrous 4-methyl-2-pentanol. MeSn(O t Bu)3 solution and 4-methyl-2-pentanol t The above solution S-4 was synthesized by mixing a second stock solution prepared of BuSn(NEt2)3 and diluting with the same solvent to achieve a total Sn concentration of 0.05 M. By this method, a series of precursor solutions were prepared by adding a total alkyl-Sn concentration ranging from 0-60 mol% as MeSn(OtBu)3. These precursor solutions were coated on 100 mm Si substrates, baked at 100 °C, and then exposed to EUV radiation at varying doses to produce contrast arrays as previously described.

[0167] After exposure, the coated wafers were baked at 170 °C in air, developed in 2-heptanone for 15 s, rinsed with a wash bottle containing the same solvent for 15 s, then dried under N2 and baked at 150 °C in air for 5 min. Fig.13 The residual thickness of each exposed panel was measured and plotted as a function of dose. The extracted resist metrics (see Example 5) are listed in Table 2. Fig.13It is observed that with the increase of MeSn(OtBu) 3mol% in the precursor solution, Dg decreases significantly, however, even at relatively low D g The contrast remains high at values ​​of <D g It is always close to zero, indicating the removal of the resist in the unexposed areas with minimal residue (scum).

[0168] Table 2

[0169]

[0170] A pattern of 18 nm lines on 36 nm pitch was exposed onto a similarly processed wafer using a Lawrence Berkeley National Laboratory micro exposure tool using 13.5 nm wavelength radiation, dipole illumination, and a numerical aperture of 0.3. Line width (CD) was measured with SEM and relative to Fig.14 Similarly, it is found that with the concentration of MeSn(O t As the mole fraction of Bu)3 increases, the amount of image forming agent required to achieve a given line width decreases strongly. Fig.15 Representative SEM images from the same wafer of precursor solutions containing a) 20%, b) 40%, and c) 60% P-6 are shown.

[0171] The above embodiments are intended to be illustrative and not restrictive. Additional embodiments are within the scope of the claims. In addition, although the present invention has been described with reference to specific embodiments, those skilled in the art will recognize that changes can be made in form and detail without departing from the spirit and scope of the present invention. Any incorporation of the above documents by reference is restrictive so that no subject matter contrary to the explicit disclosure of this article is incorporated. To the extent that a specific structure, composition and / or process herein is described together with a component, element, ingredient or other part, unless otherwise specifically specified, to some extent, it should be understood that the present invention covers specific embodiments, embodiments comprising specific components, elements, ingredients, other parts or combinations thereof, and embodiments consisting mainly of such specific components, ingredients or other parts or combinations thereof that may include additional features that do not change the basic nature of the subject matter.

Claims

1. A method for forming a radiation-patternable organic metal coating, the radiation-patternable organic metal coating comprising an oxo-hydroxy network having metal cations having organic ligands containing metal-carbon bonds and metal-oxygen bonds, the method comprising: A first precursor vapor containing a composition is introduced into a deposition chamber which is sealed and isolated from the ambient atmosphere. The composition is represented by the formula R n S X 4-n wherein n=1 or 2, wherein R is an organic ligand having 1 to 31 carbon atoms and is bonded to Sn via a metal-carbon bond, and X is a ligand having a hydrolyzable bond to Sn, and A second precursor vapor is introduced sequentially or simultaneously, the second precursor vapor comprising an oxygen-containing compound capable of reacting with the composition in the first precursor vapor under conditions in the deposition chamber to form a composition having the following components: a non-volatile component including a reaction product having an X ligand or ligand and a volatile component, wherein the substrate is configured with a surface to receive the non-volatile component of the composition.

2. The method according to claim 1, wherein: The second precursor vapor includes water vapor.

3. The method according to claim 1, wherein: The deposition chamber has a pressure of 0.01 Torr to 25 Torr.

4. The method according to any one of claims 1 to 3, wherein: The deposition chamber has a temperature of 40°C to 175°C.

5. The method according to any one of claims 1 to 3, wherein: The inputting of the first precursor vapor and the inputting of the second precursor vapor are repeated at least once to have a second deposition cycle.

6. The method according to any one of claims 1 to 3, further comprising the step of introducing an inert purge gas between each cycle of introducing the precursor vapor.

7. The method according to claim 6, wherein: The inert flushing gas is nitrogen or argon.

8. The method according to any one of claims 1 to 3, wherein: A third precursor is introduced into the chamber, wherein the precursor comprises ML v , wherein v is 2≤v≤6 and L is an oxidizable ligand or a ligand having a hydrolyzable ML bond or a combination thereof, and M is a metal selected from Group 2 to Group 16 of the periodic table.

9. The method according to claim 1 or 3, wherein: The oxygen-containing compound includes water vapor, hydrogen peroxide, ozone, oxygen, alcohol or a combination thereof.

10. The method of any one of claims 1-3, further comprising adjusting a pressure in the deposition chamber.

11. The method according to any one of claims 1 to 3, wherein: Inputting the first precursor vapor includes generating a first precursor vapor flow, generating an aerosol from a liquid comprising a first precursor composition, injecting the liquid into a vaporization chamber, flashing the first precursor vapor composition, and / or bubbling an inert carrier gas through a liquid comprising a first precursor vapor composition, wherein the first precursor vapor is formed, and wherein a radiation-patternable thin film is formed by a CVD process after the inputting step.

12. The method according to any one of claims 1 to 3, wherein: Inputting the second precursor vapor includes generating a second precursor vapor flow, generating an aerosol from a liquid comprising a second precursor composition, injecting the liquid into a vaporization chamber, flashing the second precursor vapor composition, and / or bubbling an inert carrier gas through a liquid comprising a second precursor vapor composition, wherein the second precursor vapor is formed, and wherein a radiation-patternable thin film is formed by a CVD process after the inputting step.

13. The method according to any one of claims 1 to 3, wherein: R is methyl, ethyl, isopropyl, n-butyl, sec-butyl or tert-butyl.

14. The method according to any one of claims 1 to 3, wherein: X is an alkylamide or dialkylamide; a siloxo group; a silylamide group; a disilylamide group; an alkyloxy group and an aryloxy group; an azido group; an alkynyl group; an amide group; an amido group; an imine group or a fluorinated derivative thereof, or a combination thereof.

15. The method according to any one of claims 1 to 3, wherein: A radiation-patternable thin film is formed after the input step, and the method further comprises an exposing step in which the radiation-patternable thin film is irradiated with a pattern of EUV radiation.

16. The method according to claim 15, wherein: The radiation dose is 1 mJ / cm 2 Up to 150mJ / cm 2 . 17 . The method of claim 15 , further comprising baking at 45° C. to 250° C. for 0.5 to 30 minutes after the exposing step.

18. The method of claim 15, further comprising developing the irradiated film to selectively remove non-irradiated film material or irradiated film material, and forming a pattern in the film, wherein the pattern has a pitch of no more than 60 nm, a feature width of no more than 25 nm and / or a line width roughness of no more than 5 nm.

19. The method of claim 15, further comprising developing the irradiated film to selectively remove non-irradiated film material or irradiated film material and form a pattern in the film, wherein the radiation dose is 8 mJ / cm 2 Up to 25mJ / cm 2 , wherein the pattern has a pitch of no more than 32 nm, a feature width of no more than 16 nm and / or a line width roughness of no more than 4 nm.

20. The method according to claim 15, wherein the amount of gelling agent does not exceed 5.5 mJ / cm 2 .

21. The method according to any one of claims 1 to 3, wherein: The substrate comprises a silicon wafer, wherein the radiation-patternable organometallic coating has an average coating thickness of 2 nm to 40 nm, and the average coating thickness varies by no more than + / - 50% of the average coating thickness.

22. The method according to any one of claims 1 to 3, wherein: Forming the composition includes chemical vapor deposition, physical vapor deposition, or atomic layer deposition.

23. The method of any one of claims 1-3, further comprising heating the substrate and / or the deposition chamber wall to 40°C to 175°C.

24. The method of claim 1 further comprising cooling the substrate.

25. The method of claim 14, wherein: X is -NR 1 R 2 , where R 1 and R 2 is independently a hydrocarbon group having 1 to 10 carbon atoms or hydrogen; -OSiR 1 R 2 R 3 , where R 1 , R 2 is independently a hydrocarbon group having 1 to 10 carbon atoms; -N(SiR 1 3)(R 2 ), where R 1 and R 2 is independently a hydrocarbon group having 1 to 10 carbon atoms; -N(SiR 1 3)(SiR 2 3), where R 1 and R 2 are independently a hydrocarbon group having 1 to 10 carbon atoms; -OR, wherein R is an alkyl group or an aryl group having 1 to 10 carbon atoms; -N3; ​​-C≡CR, wherein R is a hydrocarbon group having 1 to 9 carbon atoms; -NR 1 (COR 2 ), where R 1 and R 2 is independently a hydrocarbon group having 1 to 7 carbon atoms or hydrogen; -NR 1 C(NR 2 )R 3 , where R 1 and R 2 are independently a hydrocarbon group having 1 to 8 carbon atoms or hydrogen; -N(COR 1 )(COR 2 ), where R 1 and R 2 is independently a hydrocarbyl group having 1 to 8 carbon atoms or hydrogen.